RUNX3 interaction with ATRAP regulates STZ-induced T1DN injury through NLRP3 inflammasome - Juan Zhou; Xiaolin Lin; Qianqian Li; Xian Li (Tissue and Cell, 2027)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Chemical constituents of Paratinospora sagittata and their chemotaxonomic significance - Wei Nie; Zhang-Juan Li; Ye-Ting Shi; Ming Hu; Xing-De Wu; Lin-Fen Ding (Biochemical Systematics and Ecology, 2026)

Novel biallelic LSS variants in autosomal recessive hypotrichosis simplex: insights from a multi-omics approach - Xiaxia Liu; Kai Liu; Yuda Wei; Yongzhen Qi; Yangyang Luo; Tingli Chen; Xiaohua Ye; Junxu Lu; Yunjia Li; Liangqian Jiang; Juan Teng; Xingzhu Geng; et al. (Human Genetics, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Poly(phenol-imidazole) nanosheets engineered multifunctional hydrogel for promotion of infected diabetic wound healing - Jia Xin Yu; Lu Yao Li; Yu Fan; Piao Zheng; Sha Yang; Qi Fang Liu; Cai Juan Huang; Ya Lin Cao; Yang You (Chemical Engineering Journal, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Structure and bioactivity of protolimonoids from the root bark of Dictamnus dasycarpus Turcz. - Hua Yue; Zi-Xuan Li; Zi-Tong Hao; Dan Zeng; Jie Bao; Ling-Zhi Zhang; Xue-Man Lin; Hua Sun; Shu-Fang Li; Su-Juan Wang (Phytochemistry, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Divergent activation of a glutathione-tryptophan module by cysteine and hydrogen sulfide enables metabolic recovery from cyanide poisoning in rice - Yi Kang; Xing-Hui Feng; Cheng-Zhi Li; Yu-Juan Lin; Xiao-Zhang Yu (Journal of Environmental Chemical Engineering, 2026)

A hybrid soft sensing framework for cost-effective monitoring of nitrogen in wastewater treatment under data scarcity - Yaorong Shu; Zhilin Li; Jinpeng Chen; Xiaoyu Lin; Wenjun Liu; Juan Mao; Hui Liu; Feixiang Zan; Xiejuan Lu; Xiaohui Wu (Journal of Environmental Chemical Engineering, 2026)

2,6-Dibromophenol inhibits fin regeneration in zebrafish larvae via Wnt-mediated immune cell recruitment - Yuhan Huang; Wenya Tie; Zijian Li; Nannan Wang; Jiayan Xiong; Li Lin; Yuan Kong; Yunyi Mo; Minting Li; Jianpeng Liu; Zhonghao Xiao; Weitao Hu; et al. (Fish & Shellfish Immunology, 2026)

An objective detection method for tinnitus using memristors - Hui Ma; Xiaoyan Ma; Yingying Xuan; Zelin Cao; Lin Li; Kaikai Gao; Mengna Wang; Ruifeng Qiao; Qin Hu; Wentao Yan; Kun Wang; Haoyuan Wang; et al. (Chemical Engineering Journal, 2026)

Eddy vertical structure and energy in the southeastern Indian Ocean: implications for dissipation and lifespan - Yinghui He; Wenshuo Ding; Qingyou He; Xiaoming Zhai; Tongya Liu; Yankun Gong; Jieshuo Xie; Jiexin Xu; Zhiwu Chen; Juan Li; Pengfei Lin; Shuqun Cai (Progress in Oceanography, 2026)

Melatonin remodels gut microbiota and tryptophan metabolism to ameliorate methamphetamine-induced cognitive impairment - Lin Miao; Lisha Xu; Xue Yang; Yingjie Zhao; Qiaoqiao Liu; Xiaoxuan Zheng; Xinyu Zheng; Liu Liu; Jian Huang; Juan Li; Xiaofeng Zeng (Journal of Hazardous Materials, 2026)

Associations of neighborhood racial and ethnic, economical, and educational segregation with breast cancer risk: The Multiethnic ohort Study - Ugonna Ihenacho; Jenna Khan-Gates; Katherine Lin; Janine V. Abe; Pushkar P. Inamdar; Juan Yang; Yuqing Li; Meera Sangaramoorthy; Christopher A. Haiman; Loïc Le Marchand; Lynne R. Wilkens; Scarlett Lin Gomez; et al. (Cancer Causes & Control, 2026)
Purpose Residential segregation is recognized as an upstream driver of poor health, yet few studies have evaluated its impact on breast cancer incidence at a local level. We examined associations of neighborhood residential segregation with breast cancer (BC) incidence in the Multiethnic Cohort Study (MEC). Methods Measures of Index of Concentration at the Extremes were developed to assess residential segregation by income, education, race and ethnicity, and racialized income. A prospective study (1993–1996 through December 2019) was conducted to examine associations of these measures and breast cancer incidence for 101,785 African American, Japanese American, Latina, Native Hawaiian, and White female participants in the MEC, aged 45–75 years at baseline and residing in California and Hawai‘i. Multivariable Cox regression was conducted to evaluate the associations of several residential segregation measures with breast cancer incidence (cases = 7,381) adjusting for demographic, lifestyle, and reproductive factors. Results In California, BC risk was higher for females residing in neighborhoods with the highest compared to lowest concentration of privilege by income segregation (quintile 5 [Q5] vs. Q1: hazard ratio [HR] 1.12, 95% confidence interval [CI] 1.00–1.25, P trend = 0.001) and education segregation (Q5 vs. Q1: HR 1.15, 95% CI 1.01–1.31; P trend = 0.01). For Latina females, risks increased with increasing privilege for measures of income, education, race and ethnicity, and racialized income residential segregation ( P trends < 0.05). No associations were observed in Hawai‘i. Conclusion In California, residential economic privilege was independently associated with increased BC risk. Future studies should examine neighborhood- and individual-level pathways placing females residing in privileged areas at greater risk.

Removal of antibiotics by an oleaginous green microalga Chromochloris zofingiensis under photoautotrophic, heterotrophic and mixotrophic conditions - Kai-Lu Cao; Juan Peng; Meng-Zhen Li; Lin-Yun Liao; Zi-Wen Song; Hong-Zhi He; Jun Zhao (Algal Research, 2026)

Bias correction and future projection of precipitation concentration and structure in the Three River Headwaters Region - Juan Du; Li Zhou; Xiaojing Yu; Chanwen Jiang; Lin Zhang; Yunfei Gao (Climatic Change, 2026)

Retraction notice to “Applying thallium isotopic compositions as novel and sensitive proxy for Tl(I)/Tl(III) transformation and source apportionment” [Sci. Total Environ. 913 (2024) 169542] - Juan Liu; Lulu Wang; Jingfen Lin; Wenhuan Yuan; Liangzhong Li; Yung-Kang Peng; Xinni Xiong; Huimin Cao; Xudong Wei; Qi'en Ouyang; Holger Lippold; Jin Wang; et al. (Science of The Total Environment, 2026)

Genomic landscape of idiopathic male infertility and the pregnancy outcomes following assisted reproductive technology - Chen Tan; Tongyao Hu; Lanlan Meng; King Kin Lam; Qing Zhang; Xilin Xu; Shimin Yuan; Yurong Wang; Zilan Huang; Keren Zhou; Yong Li; Chunbo Xie; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Metabolic rewiring and transcriptional interference underlie the biocontrol efficacy of Burkholderia arboris BB417 against Ralstonia solanacearum species complex - Shanwen Ding; Juan Zhang; Yang Wang; Guobing Lan; Lin Yu; Yafei Tang; Zhenggang Li; Bin Guo; Zifu He; Xiaoman She (Pesticide Biochemistry and Physiology, 2026)

Industrial waste salt pyrolysis toward zero liquid discharge: Enabling efficient organic removal and resource recovery - Zhi-Bo Li; Xiang-Lin Chang; Juan Xie; Rong Chen; Xiaochang C. Wang; Bao-Shan Xing (Journal of Water Process Engineering, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

The undescribed alkaloids from Jacobaea cannabifolia (less.) E. Wiebe and their anti-inflammatory activities - Jian-Zhe Li; Juan Pan; Yu Bi; Zhi-Chao Hao; Wei Guan; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Xin-Yue Wu; Da-Lin Li; Bing-You Yang; Yan Liu (Natural Product Research, 2026)

Rockburst mitigation by microwave destressing in a deep drill-and-blast tunnel: thermal–damage–stress evolution with a slotted-wall coaxial applicator - Yuntan Ao; Xia-Ting Feng; Shiping Li; Xiaojun Zhang; Juan He; Tianyang Tong; Yifan Zhang; Feng Lin (Tunnelling and Underground Space Technology, 2026)

Immunoglobulin M response in different intestinal segments of largemouth bass (Micropterus salmoides) following largemouth bass virus (LMBV) infection - Xinyou Wang; Gaofeng Cheng; Jie Sun; Chang Cai; Zhihao Jiang; Ruiqi Lin; Shun Li; Li Li; Juan Zhao; Zhen Xu; Weiguang Kong (Fish & Shellfish Immunology, 2026)

Synergistic enhancement of rhodamine 6G fluorescence by photonic crystals and β-cyclodextrin for sensitive detection of EGCG - Lu Li; Xinyan Chen; Yuxuan Zhang; Luqiao Tian; Chaoran Lei; Miao Lin; Juan Wei; Dejian Huang; Yongquan Xu; Guiqiang Fei (Chemical Engineering Journal, 2026)

A BRIGHT platform advances integrated hazard indexing toward actionable control of human pathogenic bacteria in residential buildings - Qisheng Li; Huan Liu; Ling N. Jin; Lumeng Liu; Hua Zhou; Wenmao Zeng; Yingxian Zhai; Tian Chen; Jinyan Yu; Dongdong Su; Juan Lin; Qian Wang; et al. (Building and Environment, 2026)

Adenosine A1 receptor in the medial parabrachial nucleus modulates sleep-wake regulation and homeostatic processes - Minrui Zhao; Jin Huang; Yue Zhang; Ronghua Liao; Lin Zhang; Hongxia Li; Juan Wang (Sleep and Biological Rhythms, 2026)

Tinosporoside E and tinosporane A: two new clerodane diterpenes from the tuberous roots of Paratinospora sagittata - Li Fan; Yu-Jie Zhang; Shi-Peng Zhang; Wan-Shu Li; Ling-Juan Zhu; Hang-Juan Lin (Natural Product Research, 2026)

Bioactive coumarins and chromones with anti-neuroinflammatory effect from Gerbera piloselloides - Cong Zhang; Kuan Lin; Qing-Qin He; Hao Gong; Li-Juan Hu; Mei Zhou; Shi Chen; Wei Liu; Xian-Sheng Ye; Xi-Ji Shu (Phytochemistry Letters, 2026)

RNAi against ribosomal protein L27 gene impairs larval development in Phthorimaea operculella - Yu Zhang; Zhong-Yuan Wang; Ya-Hao Rao; Juan Peng; Lin Jin; Guo-Qing Li (Journal of Asia-Pacific Entomology, 2026)

Corrigendum to “Hellebrigenin induces cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells through inhibition of Akt” [Chemico. Biol. Interact. 219 (2014) 184-194] - Li-Juan Deng; Li-Ping Hu; Qun-Long Peng; Xiao-Lin Yang; Liang-Liang Bai; Anita Yiu; Yong Li; Hai-Yan Tian; Wen-Cai Ye; Dong-Mei Zhang (Chemico-Biological Interactions, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Genetic analysis and reproductive interventions in families affected by congenital cataracts: a study of 107 cases - Yun-hao Li; Qi Wang; Yao Peng; Juan Du; Liang Hu; Zhen-hua Tan; Feng Gu; Hao Hu; Qian-jun Zhang; Ge Lin; Guang-xiu Lu; Yue-Qiu Tan; et al. (Journal of Applied Genetics, 2026)

Talarombrevisone A, an β -aminopropionate with two polyketide units, isolated from an endophytic fungus Talaromyces brevis - Yun-He Tuo; Zhong-Duo Yang; Jian-Guo Chen; Cui-Juan Xu; Lin-bo Liu; Tian-Kun Zhao; Yue Li; Li-Bin Xia; Shuai Yu; Ai-Hong Zhao; Shuo Li (Natural Product Research, 2026)

Leaf functional traits and wood density of evergreen and deciduous tree species in a tropical karst forest - Yu-Meng Gao; Shi-Jian Yang; Jiao-Lin Zhang; Yan-Juan Jiang; Shu-Bin Zhang; Amy Ny Aina Aritsara; Guo-Hao Hu; Pei-Li Fu; Ze-Xin Fan; Kun-Fang Cao (Flora, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

High-value utilization of chromium ore processing residue (COPR) through corn straw-soda roasting followed leaching processes - Cheng Tian; Zilong Li; Cunfang Lu; Rui Xu; Min Zhang; Lin Yang; Wenlin Xie; Zhengnan Zhong; Yuanyuan He; Juan Wen; Dan Luo (Journal of Environmental Chemical Engineering, 2026)

In-situ construction of novel dual bismuth–rich Bi4O5Br2/Bi7O9I3 S-scheme heterojunction with enhanced photocatalytic activity for degradation of diverse persistent organic pollutants - Jia-Lin Zong; Hui-Long Wang; Hao Huang; Yi-Hui Zhao; Li-Juan Han; Wen-Feng Jiang (Journal of Environmental Chemical Engineering, 2026)

Sustained performance and microbial succession in novel artificial rumen system coupling dynamic membrane with methanogenic granules for acid absorption - Xiang-Lin Chang; Bao-Shan Xing; Yu Qin; Juan Xie; Zhi-Bo Li; Xiaochang C. Wang; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

In situ cultivation and chromogenic screening: a dual approach for rapid discovery of PDE1 inhibitors from pinus-tree associated microbes - Cui-Juan Xu; Shuo Li; Zhong-Duo Yang; Lin-Bo Liu; Yun-He Tuo; Yong-Jiao Niu; Lei-Lei Chen; Jian-Guo Chen; Tian-Kun Zhao; Ai-Hong Zhao (World Journal of Microbiology and Biotechnology, 2026)

An efficient embryogenic cell suspension enabling somatic embryogenesis in Phyllostachys edulis - Simeng Kong; Huan Liu; Kaiting Wang; Xiaohong Zhou; Xinyi Yang; Juan Zhuo; Xiangyu Li; Xinchun Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Effect of 6-Month High-Impact and Resistance Exercise on Regional Strength and BMD of Spine: A Clinical Trial Combined with a Finite-Element Study - Pu Duan; Yinxia Nie; Shizhong Liu; Xiaoyu Xia; Rui Xu; Simin Li; Vadim V. Silberschmidt; Lin Meng; Juan Du; Dong Ming (Annals of Biomedical Engineering, 2026)

Integrated LC-Orbitrap-MS and network pharmacology decipher the pharmacological basis of Eucommiae folium in treating rheumatoid arthritis - Yasi Deng; Ling Liang; Haokai Lin; Xinyang Shen; Hao Zheng; Ying Deng; Xing Tian; Juan Huang; Ye Zhang; Bin Li; Huanghe Yu; Wei Wang (Molecular Diversity, 2026)

Spatiotemporal variations in indoor thermal environments and dynamic comfort of passengers in airport terminals during winter - Yuxin Yang; Juan Yu; Deyin Zhang; Hao Tang; Wenzhong Jiang; Libin Han; Junmin Li; Borong Lin; Yu Dong (Building and Environment, 2026)

The Time Reliable Effect of Probiotic Clostridium butyricum on the Growth of Spotted Sea Bass (Lateolabrax maculatus) - Yiqin Deng; Liwen Xu; Keng Yang; Ziyang Lin; Shujun Zang; Kui Jiang; Wangdong Li; Nabil A. Ibrahim; Hongling Ma; Changhong Cheng; Juan Feng (Probiotics and Antimicrobial Proteins, 2026)

Soybean Hyperspectral Leaf Area Index (LAI) Estimation Based On Soil-vegetation Separation Algorithm and Derivative Spectroscopy - Nai-ning Zhong; Yu-lin Liu; Yi-zheng Zhao; Yi-xuan Mei; Hao-lin Shen; Xin-Zhou Lei; Yu-ning Wu; Juan-li Ju; Youzhen Xiang (Journal of Soil Science and Plant Nutrition, 2026)

Intrinsic capacity across the adult lifespan in China: baseline analysis from the nationwide longitudinal PENG ZU cohort - Ju Cui; Yujia Gu; Jing Pang; Huafang Gao; Li-Qun Zhang; Xiaolan Wu; Junwu Dang; Juan Li; Xinyi Zhu; Senlin Luo; Zhao Wang; Fuyi Tu; et al. (GeroScience, 2026)

PRDX6 as a Ferroptosis-Related Hub Gene in the Entorhinal Cortex of Alzheimer’s Disease: A Multidimensional Bioinformatics and Experimental Validation Study - Xiaolin Li; Ziteng Man; Tiantian Cheng; Juan Song; Yanan Bao; Yu Lin; Hongyan Yang (Journal of Molecular Neuroscience, 2026)

Histone H3.3 phosphorylation facilitates H3K9me3-heterochromatin formation during retrotransposon silencing and X-chromosome inactivation via H3.3K27me3–CBX7–KAP1 axis - Jun Chen; Jiyu Chen; Zhouliang Yu; Liwei Zhang; Yanchao Liu; Xuan Ouyang; Juan Yu; Menghan Wang; Shangqiang Xie; Ming Wang; Tiantian Zhang; Zhaohui Jin; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Exploring different modification methods of biochar for Se(IV) removal from water: Synergistic effect of adsorption and reduction - Yu-Ying Wang; Juan Yu; Rong-Ting Jiao; Li-Li He; Yao Su; Yun-Long Wang; Hui Lin; Yan Shi; Hao-Hao Lyu (Journal of Contaminant Hydrology, 2026)

Solar-tracking photovoltaic systems create divergent microhabitats that enhance vegetation recovery in arid sandy lands - Weifeng Liu; Minghao Lu; Juan Pinos; Zhigang Li; Jingxue Zhao; Yulei Ma; Gao-Lin Wu (Journal of Arid Environments, 2026)

Reduction mediated iodide antioxidation: “Chemical Preservation” of precursor solution facilitates construction of high efficiency and stable wide bandgap inverted perovskite solar cells - Chao Liu; Yingchen Li; Hongkun Cai; Boyan Li; Shuping Lin; Qi Sun; Dalong Zhong; Jifeng Liu; Qinwen Guo; Zhiwen Xu; Juan Li; Jian Ni; et al. (Chemical Engineering Journal, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Lecithin supplementation to HFD improves largemouth bass liver health: Implications for regulating lipid homeostasis, antioxidant responses and endoplasmic reticulum stress - Biao Wang; Hua Zheng; Juan Xiong; Hong-Jun Yang; Qing-Lin Li; Zhi Luo (Fish Physiology and Biochemistry, 2026)

Immunotherapy checkpoint inhibitor-combination therapy versus chemotherapy alone among Chinese population in cholangiocarcinoma treatment: a systematic review and meta-analysis - Li Shi; Wei Du; Juan Miao; Xi-Yuan Peng; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Si-Qi Gao; Hong-Lin Chen (European Journal of Clinical Pharmacology, 2026)

Reconstructing the invasion history of the bark beetles Orthotomicus erosus and Cyrtogenius luteus (Coleoptera, Curculionidae, Scolytinae) in South America - Leonel Stazione; Carolina Soliani; Anthony Cognato; Demian F. Gomez; Dimitrios Avtzis; Edgar Eskiviski; Gonzalo Martinez Crosa; Wei Lin; You Li; Juan Corley; Victoria Lantschner (Biological Invasions, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Eight new dammarane-type triterpenoid saponins from Gynostemma pentaphyllum - Gang Li; Guang Yang; Xiao-juan Chen; Peng-xin Lu; Hai-zhen Liang; Mei-yan Wang; Jie Zhang; Bao-lin Guo; Bai-ping Ma (Natural Product Research, 2026)

Dicyanoisophorone-based near-infrared fluorescent probe with a large Stokes shift for the detection and bioimaging of hydrazine - Hong-Cheng Xia; Yu-Hang Zhang; Li-Ming Lv; Di Han; Hong-Kun Yang; Hui-Juan Yan; Jie-Li Lv; Jun-Tang Lin; Ying-Ying Kong (Journal of Hazardous Materials, 2026)

Trace-amount phenolphthalein surface-modified Na2CO3 for enhanced low-temperature dry SO2 capture via altered product layer structure - Huan Wang; Longyuan Lin; Zhongkai Zhao; Shenglong Huang; Juan Lǖ; Hong Li; Zhongbin Liu; Haiyan Chen (Journal of Hazardous Materials, 2026)

The chemotaxonomic significance of chemical constituents from Gynostemma pentaphyllum - Hou-Lin Peng; Man-Hui Yang; Wu-Di Zhai; Wen-Juan Li; Jing Liu; Yan Zhang (Biochemical Systematics and Ecology, 2026)

Oroxin A suppresses non-small cell lung cancer via the HSP90AA1/AKT signaling pathway - Mingxiao Wang; Yong Zhang; Ruoyang Liu; Juan Lin; Tengfei Wang; Huijun Dong; Ju Yang; Xiuyuan Li; Dehai Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

The centennial legacy of disturbances on sedimentation and carbon burial in an estuarine mangrove ecosystem, South China - Juan Su; Yaobei Lin; Penghui Li; Zhangcai Qin; Luhua Xie; Fan Wang; Weiguang Li; Jinghong Zhang (Journal of Oceanology and Limnology, 2026)

Comparative study on organic composts in blueberry: insights into soil physicochemical properties and heavy metal control - Hao Tang; Ying Dai; Lijuan Tang; Juan Guo; Ke Wen; Fangke Yuan; Lin Li; Yuan Jin; Jinlu Li; Min Xiao; Heng Xu (Environmental Geochemistry and Health, 2026)

Two new phenylethanol glycosides from the roots of eleutherococcus senticosus (rupr. et maxim.) maxim - Jia-Tong Wu; Ke Xiao; Hao-Lin Yang; Hui-Chen Zhu; Si-Yi Wang; Juan Pan; Meng-Meng Li; Wei Guan; Hai-Xue Kuang; Yan Liu (Natural Product Research, 2025)

Bioactive sesquiterpene lactones with cytotoxic activity from Youngia japonica - Hao Gong; Kuan Lin; Lei Zhang; Yi Huang; Li-Juan Hu; Xiao-Ya Liu; Hao Ming; Si-Qi Wang; Qing-Qin He; Xian-Sheng Ye; Shu-Xiu Zhu (Phytochemistry Letters, 2025)

Evaluation of the lipolytic and antioxidant activities of different strains of coagulase-negative staphylococci in fermented sausages - Dan Li; Yuyu Du; Liya Su; Yaqiu Lin; Jiong Zheng; Fidel Toldrá; Chenglin Zhu; Muying Du; Yuan Liu; Juan Chen (Meat Science, 2025)

Innovative cellulose-based porous matrix loaded with carvacrol microemulsion for sustainable mango preservation - Linyun Mou; Jianlong Li; Ya Lu; Lin Wu; Guijun Bu; Juan Li; Ganpeng Li (International Journal of Food Microbiology, 2025)

A new 2-arylbenzofuran derivative and other constituents from Smilax china L. and their chemotaxonomic significance - Li-Juan Hu; Xian-Sheng Ye; Kuan Lin; Jie Gao; De-Sen Yang; Guo-Ping Gan; Xi-Ji Shu; Wei Liu; You-Hua Yang (Biochemical Systematics and Ecology, 2025)

Weakened invasion of severe fever with thrombocytopenia syndrome bunyavirus beneficial to its immune escape by multi-site mutation of glycoprotein - Lin Wang; Jingjing Wang; Juan Zhang; Xin Wang; Weiyou Cao; Lilan Yang; Yulong Wu; Boqing Li; Yuanyuan Qiao (Molecular Genetics and Genomics, 2025)

Effects of Nitrogen Deposition, Biodiversity and Climate on Productivity in a Large Temperate Forest Region - Jie Li; Senxuan Lin; Minhui Hao; Chunyu Fan; Juan Wang; Klaus von Gadow; Chunyu Zhang; Xiuhai Zhao (Global Ecology and Biogeography, 2025)
Aim Nitrogen deposition is a widespread global change driver that significantly affects terrestrial ecosystems. However, evidence on the specific mechanisms of productivity response to nitrogen deposition in temperate forests across ecological and climatic gradients is scarce. This study evaluates the effects of nitrogen deposition, multiple attributes of biodiversity and climate on productivity in a large temperate forest region. Location North‐eastern China. Time Period 2017. Major Taxa Studied Woody plants. Methods We assessed taxonomic, functional, and phylogenetic attributes of tree diversity and functional identity of forest communities across a wide range of ecological and climatic conditions. Using partial linear mixed models (LMMs), multivariate LMMs, and structural equation modelling, we investigated the effects and pathways of nitrogen deposition, biodiversity, and climate conditions on productivity. We also explored the relationship between nitrogen deposition and productivity across biotic and climatic gradients. Results Our results show that nitrogen deposition, phylogenetic diversity (PD), and the community‐weighted mean of maximum tree height (CWMHM) are significant positive drivers of productivity. Climate conditions primarily affected productivity indirectly through PD. In species‐poor high‐latitude forests characterised by cold and dry climates, nitrogen deposition had strong positive effects on productivity. That effect weakened towards warmer climatic conditions. Main Conclusions The findings of this study suggest that the response of productivity to nitrogen deposition depends on local ecological and climatic conditions. Our results underscore the importance of considering interactions among multiple global change drivers to improve the accuracy of ecosystem response predictions.

Network pharmacology, molecular docking and experimental validation to elucidate the anti-ulcerative colitis mechanism of Rosa roxburghii Tratt. leaves - Ming-Liang Luo; Shuang Zhang; Qing-Yong Wang; Ling-Wei Fu; Li-Juan Xiang; Chang Lin; Xin Yin (Natural Product Research, 2025)

Formation of reactive oxidants from Fe(II)-bearing minerals in oxic environments: A review - Jieyun Lin; Juan Zhou; Yu Fu; Jiamin Cai; Shi Chen; Tao Wang; Jiang Li; Shaoqi Zhou; Yuanyuan Liu (Journal of Hazardous Materials, 2025)

Unlocking biochar's carbonyl group: Fe-Mn oxide synergy enables high-efficiency As(III) immobilization via non-radical oxidation - Zihang Cheng; Yilin Wu; Ruiqi Du; Mingming Lin; Jingzi Beiyuan; Juan Liu; Peng Liu; Bowen Li; Xueding Jiang; Hailong Wang (Journal of Environmental Management, 2025)

UPRS-1: A regolith simulant of Utopia Planitia, Mars - Yiming Diao; Honglei Lin; Juan Li; Shouding Li; Changyi Xu; Zhaobin Zhang; Zongyu Yue; Bo Zheng; Xiukuo Sun; Tao Xu; Xinshuo Chen; Yanfang Wu; et al. (Icarus, 2025)

Effects of lactic acid fermentation on the biomethanation of food waste in two-stage anaerobic digestion - Wenxue Hou; Xindong Wang; Tian Tian; Juan Wang; Benyi Xiao; Lin Li (Fuel, 2025)

Photoresponsive leaf-like structured two-dimensional metal-organic framework/nanocellulose crystal composites for efficient and rapid adsorption of pollutants from wastewater - Saisai Li; Luying Wang; Juan Dai; Na Zhang; Li Zhao; Shuyun Zheng; Xinxin Li; Caicai Lin; Dashuai Zhang; Qiang Li (Chemical Engineering Journal, 2025)

Organoids in Genetic Disorders: from Disease Modeling to Translational Applications - Yuanhang Zhu; Nanshan Lin; Juan Li; Haoqian Zhang; Ping Zhang; Xin Cheng; Qian Yang; Ling Liu (Stem Cell Reviews and Reports, 2025)

Isolation and Genomic Characterisation of Lymphocystivirus platichthys1 in Brackish‐Water Cultured Spotted Seabass Lateolabrax maculatus in Zhuhai, South China - Hongling Ma; Changhong Cheng; Yiqin Deng; Zhixun Guo; Yong Li; Guangxin Liu; Huajian Lin; Liwen Xu; Juan Feng (Journal of Fish Diseases, 2025)
Lymphocystis disease virus (LCDV) stands as one of the most widespread causative agents affecting a diverse array of teleost globally. According to the literature, LCDV encompasses four species, and Lymphocystivirus paralichthys1 (known as LCDV‐C) has long been regarded as the predominant national epidemic isolate in mainland China. In this study, two instances of severe mass mortalities associated with LCDV in brackish‐water cultured juvenile spotted seabass in Zhuhai, South China, were monitored starting from early April 2023. The death toll in these two cases peaked at approximately 4000 and 10,000 fish per day, respectively, with cumulative mortalities reaching around 70% within 19 days of the disease outbreak. Based on clinical symptoms, histopathological analyses and transmission electron microscopy observations, the diseases were diagnosed as LCDV infections. The virus was isolated using the Mandarin fish fry (MFF‐1) cell line and named LCDV‐ZH04/23. Subsequently, LCDV‐ZH04/23 was roughly purified, and its entire genome was sequenced and annotated. The results indicated that ZH04/23 consists of 102,661 base pairs, encodes 108 putative viral genes and has a G/C content of 29.3%. Genomic collinearity analysis revealed that the whole genome of ZH04/23 exhibits the highest similarity (99.9%) to the well‐known Lymphocystivirus platichthys1 (LCDV‐1) from Europe, but shows significant divergence from the other three LCDV species. Collectively, this study marks the first isolation and characterisation of L. platichthys1 at the whole genome level from cases of severe mass mortalities in pond‐cultured spotted seabass in China. Moreover, it is the first to identify L. platichthys1 as an emerging pathogen in cultured spotted seabass.

Three new triterpenoids from the fruit of Eleutherococcus senticosus (Rupr.) Harms - Yan Liu; Yu-Xuan Lin; Xiao-Hui Rong; Meng-Meng Li; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2025)

Oleic acid inhibits the proliferation, invasion, and migration of tongue squamous cell carcinoma cells under high glucose conditions through S100A9-HK2/PKM2-SOD2 signaling pathway - Yujie Ma; Runqiang Liu; Juan Zhan; Yihan Lai; Sicheng Li; Wei Wang; Yisen Shao; Lin Jiang (Tissue and Cell, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

Synergistic solar-magnetic desalination via covalently anchored Fe₃O₄/hydrogel composites - Juan Du; Hao Fang; Jialiang Ma; Jing Lin; Shikuo Li; Yu Jiang; Fangzhi Huang (Chemical Engineering Journal, 2025)

Lactiplantibacillus plantarum RS20D Alleviates Male Reproductive Toxicity Induced by Pubertal Exposure to Di-n-butyl Phthalate and Mono-n-butyl Phthalate - Yuan-ting Zhu; Xing-jie Wang; Shu-liang Liu; Jing-hui Lai; Jian-long Li; Qin Li; Kai-di Hu; Ai-ping Liu; Yong Yang; Li He; Shu-juan Chen; Xiao-lin Ao; et al. (Probiotics and Antimicrobial Proteins, 2025)

Biocontrol mechanism of a newly isolated Streptomyces sp. JL2001 against Ralstonia solanacearum via aerugine - Zixian Zeng; Wei Cao; Hong Pu; Dousheng Wu; Sai Jiang; Meng Su; Yajing Wang; Zhi Wang; Xin Zhao; Juan Li; Shunxiang Li; Lin Jiang (Pesticide Biochemistry and Physiology, 2025)

Fabrication of multicolor fluorescent perovskite-polymer composites and their application in information encryption - Yihui Lei; Huiling Liang; Lin Bai; Mingyu Jin; Juan Cheng; Tingcheng Li; Daohong Zhang; Sufang Chen; Zejun Xu (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A critical need to control thallium contamination in aquatic ecosystem for the age of low carbon - Juan Liu; Wenhuan Yuan; Yu Shi; Yanyi Liu; Pei Li; Wanpeng Chen; Xuan Zeng; Ying Li; Ke Lin; Yinyin Lu; Haiyao Hu; Jin Wang (Journal of Hazardous Materials, 2025)

Strain-specific effects of fish originated Bacillus velezensis on growth, gut health, and disease resistance of zebrafish - Yuan-Yuan Yao; Wen-Hao Zhou; Juan Hu; Ya-Lin Yang; Ming Li; Rui Xia; Chao Ran; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2025)

Magnetically-driven Dual-channel Fluorescent Biosensor with Aptamer Logic Gates for Multiplexed Exosomal Protein Profiling and Breast Cancer Subtyping - Yanqiu Wu; Lin Chen; Yao Tong; Changsheng Zhai; Guiyong Xiao; Yupeng Lv; Lutao Du; Juan Li; Peng Ren; Yanyan Jiang (Chemical Engineering Journal, 2025)

Micropatterned piezoelectric films induced by modulated corona field for weak signal detection - Fu Lv; Chenghang Yu; Bing Liu; Jiamin Lin; Zijian Hong; Yongjun Wu; Zhaohui Ren; Qilong Zhang; Shurong Dong; Jikui Luo; Juan Li; Yuhui Huang (Chemical Engineering Journal, 2025)

Moxibustion pre-treatment attenuates seizure severity during status epilepticus and counteracts the proconvulsant function of the purinergic P2X7 receptor - Hong-Wei Zhang; Jia-Jia Li; Yulihan Tang; Mao-Lin Tian; Sheng Huang; Meng-Juan Sun (Purinergic Signalling, 2025)

Direct recovery of high-purity uranium from fluoride-containing nuclear wastewater via extraction materials with ensemble Lewis sites and a tandem electrochemical device - Guo Li; Yan Liu; Chi Jiao; Zhengyu Jiang; Juan Zhang; Tao Chen; Tao Lin; Rong He; Wenkun Zhu; Xiangke Wang (Water Research, 2025)

Unravelling the pathogenesis of Vibrio parahaemolyticus infection: impacts on antioxidant and innate immunity gene responses in Scylla paramamosain - Guangxin Liu; Ce Li; Sigang Fan; Hongling Ma; Yiqin Deng; Jianjun Jiang; Changhong Cheng; Juan Feng; Li Lin; Zhendong Qin; Zhixun Guo (Fish & Shellfish Immunology, 2025)

A self-powered photocatalytic fuel sensor for single-cell analysis with high reliability - Kejun Guo; Lin Zhong; Su Li; Xiya Liu; Junjie He; Linjing Liu; Juan Wang (Chemical Engineering Journal, 2025)

pH-responsive drug-targeted delivery system: Dual-drug loading hollow mesoporous silica for synergistic therapy bacterial enteritis of Micropterus salmoides - Yuan-shuai Fu; Yue Lin; Wen-jun Zhong; Xing-yu Wang; Xi-ke Li; Yun-ao Li; Sheng-bo Ye; Wen-juan Li; Yong-heng Zhu (Chemical Engineering Journal, 2025)

Preparation and characterization of Salecan β-glucan-based edible film loaded with lemon essential oil nanoemulsion: Effects on the preservation of chilled pork - Jiao Lin; Juan Dai; Qian Yang; Jiarui Li; Jing Xiao; Yuexin Zhang; YuKun Huang; Lijun Wang; Pengfei Chen; Buyi Xu; Juan Zhao; Xiao Yang; et al. (Food Chemistry, 2025)

Time series comparative genomics analysis reveals the adaptive evolution of caproic acid-producing bacteria to the long-term liquor brewing environment - Gan-Lin Li; Jun-Lan Mei; Li-Juan Chai; Xiao-Zhong Zhong; Ya-Ning Song; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2025)

Determination of the spatiotemporal evolution patterns and obstacle factors of coupling coordination of the water–energy–food–ecology system in Ordos City, China - Jihong Qu; Jixian Lin; Mengting Cheng; Zezhong Zhang; Kai Feng; Fei Wang; Kun Ren; Juan Zhou; Yanbin Li (Environmental Geochemistry and Health, 2025)

Developmental and reproductive toxicity (DART) study of a novel SARS-CoV-2 tetravalent recombinant protein vaccine (SCTV01E) in rats - Xiao Zhang; Jilei Jia; Gaojian Chen; Dan Meng; Juan Ma; Huimin Wang; Shaozheng Zhou; Lin Ma; Qianqian Qian; Xuejie Liu; Xuefeng Li; Liangzhi Xie (Reproductive Toxicology, 2025)

Leveraging ionic information for machine learning-enhanced source identification in integrated wastewater treatment plant - Yaorong Shu; Fanming Kong; Xiaoyu Lin; Jinpeng Chen; Wenjun Liu; Zhilin Li; Juan Mao; Xiaohui Wu (Journal of Water Process Engineering, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

Methamphetamine and HIV-1 Tat Protein Synergistically Induce Endoplasmic Reticulum Stress to Promote TRIM13-Mediated Neuronal Autophagy - Chan Wang; Genmeng Yang; Jian Huang; Yunqing Tian; Chi-Kwan Leung; Lin Miao; Haowei Wang; Yi Li; Yizhen Huang; Hanxin Teng; Liu Liu; Juan Li; et al. (Molecular Neurobiology, 2025)

Soil viruses regulate soil nutrient cycling through themselves and their effects on host functioning to impede the growth of continuously planted Casuarina equisetifolia - Yu-Hua Wang; Lei Hong; Yi Lin; Miao-En Qiu; Jian-Juan Li; Qing-Xu Zhang; Xiao-Li Jia; Yu-Lin Wang; Li-Yuan Wang; Yang-Xin Luo; Wen-Xiong Lin; Hai-Bin Wang; et al. (Applied Soil Ecology, 2025)

Spatial adaptations in hospitality amid COVID-19: A case study of Xiamen's B&B sector - Juan Lin; Han Li; Shuyu Xing; Weiye Xiao (Applied Geography, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

MiR-518b Promotes the Tumorigenesis of Hepatocellular Carcinoma by Targeting EGR1 to Regulate PI3K/AKT/mTOR Signaling Pathway - Xinyuan Wang; Juan Li; Jiao Nong; Xin Deng; Yiping Chen; Bing Han; Lin Zeng; Xiabing Huang (Cell Biochemistry and Biophysics, 2025)

Genome-wide association analysis reveals genetic loci and candidate genes for white diarrhea in Jingyuan chickens - Lijuan Yang; Siyu Chen; Wei Zhao; Guojun Zhang; Hu Zhang; Tong Zhang; Lin Xue; Jinli Tian; Yaling Gu; Lanlan Li; Hu Wang; Juan Zhang (Research in Veterinary Science, 2025)

Differences in Pathogenetic Mechanism Between Tibetan and Han High-Altitude Polycythemia Based on a Whole Genome-Wide Association Study - Zhuoma Basang; Shixuan Zhang; Xianwei Ke; Zhuoma Duoji; La Yang; Danzeng Qiangba; Yang De; Deji Gesang; Zixin Hu; Yanyun Ma; Meng Hao; Ruidong Fan; et al. (Phenomics, 2025)

The Role and Mechanism of TRIM13 Regulation of TRAF6 Ubiquitination in the Synergy of Inflammatory Responses and Neurotoxicity Induced by METH and HIV- 1 Tat Protein in Astrocytes - Yi Tan; Lin Miao; Chan Wang; Haowei Wang; Yi Li; Yizhen Huang; Hanxin Teng; Yunqing Tian; Genmeng Yang; Xiaofeng Zeng; Juan Li (Neurotoxicity Research, 2025)

Application of Artificial Intelligence in Identifying Human Immunoglobulin and Albumin in Commercial Intravenous Drugs - Juan Padierna-Olivos; Juan Francisco Sánchez-Ruiz; Gustavo Alonso Martínez-Blanco; Carlos Arturo Medina-García; Brenda Magali Lin-Li Lagunas-Bucio; Ariadna Rosas-Hernández; Cecilia Padierna-Mota; Alberto Padierna-Mota; Carlos Gershenson-García (Journal of Pharmaceutical Innovation, 2025)

Decade-long application of preimplantation genetic testing for DMD/BMD: analysis of five clinical strategies and embryo recombination patterns - Weili Wang; Jing Dai; Xiao Hu; Wenbin He; Yifan Gu; Zhenxing Wan; Yi Zhang; Keli Luo; Wen Li; Qianjun Zhang; Fei Gong; Guangxiu Lu; et al. (Human Genetics, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Evaluation of Heavy Metals and Essential Minerals in the Hair of Children with Autism Spectrum Disorder and Their Association with Symptom Severity - Xulan Zhou; Xiaochun Xia; Liming Li; Yaohui Ye; Qihui Chen; Mingyue Ke; Qian Cui; Yuling He; Yiting Chen; Shaoqing Lin; Wenlong Liu; Juan Wang (Biological Trace Element Research, 2025)

CAR-NK cell therapy: a potential antiviral platform - Ming-Hao Lin; Li-Juan Hu; Jeffrey S. Miller; Xiao-Jun Huang; Xiang-Yu Zhao (Science Bulletin, 2025)

Sesquiterpenoids from Inula britannica and their potential mechanism for immunomodulation - Hui-Lin Zhang; Na Wang; Xu-Liu Shi; Miao-Miao Wang; Qi-Meng Zhu; Jing Chang; Yan-Li Feng; Juan Zhang; Feng Qiu; Cheng-Peng Sun (Phytochemistry, 2025)

The role of coagulase-negative staphylococci on aroma generation of fermented sausage - Juan Chen; Shenmiao Li; Yaqiu Lin; Fidel Toldrá; Xiaonan Lu (Meat Science, 2025)

Uncovering toxin production and molecular-level responses in Microcystis aeruginosa exposed to the flame retardant Tetrabromobisphenol A - Li Yin; Yu Yin; Lin Xu; Yong Zhang; Kaipian Shi; Juan Wang; Junfeng An; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Journal of Hazardous Materials, 2025)

Untargeted qualitative and targeted quantitative analysis of saponins reveal differential chemotypes of Gynostemma pentaphyllum and G. longipes from different geographical origins - Hai-Zhen Liang; Mei-Yan Wang; Guang Yang; Gang Li; Jie Zhang; Lan Yao; Yi Nan; Chang-Liang Huang; Xiao-Juan Chen; Juan Song; Feng Cao; Bao-Lin Guo; et al. (Food Chemistry, 2025)

High electrocatalytic activity of crystallization-modulated ordered PtCu3/C nanoalloy catalysts for oxygen reduction reaction - Xiaomei Li; Linfeng Fu; Lin Cao; Lihui Lei; Xinxing Zhan; Changgang Hu; Xin Tong; Juan Tian (Chemical Engineering Journal, 2025)

Enhanced synergistic effect of acidity and active phase for Ni-Co@NHZ-5-AT on hydroconversion of benzyoxybenzene to polycyclic alkanes - Xiao-Wei Yu; Yan-Jun Li; Yu-Hong Kang; Juan Gao; Pei-Lin Yang; Guang-Hui Liu; Shou-Long Gong; Xiao-Yu Kang; Yong Gao; Xian-Yong Wei; Wei Lu (Biomass and Bioenergy, 2025)

Bamboo - A potential lignocellulosic biomass for preparation of hard carbon anode used in sodium ion battery - Gengchen Li; Zifeng Hua; Juan Yang; Heshen Hu; Jiefeng Zheng; Xiaojuan Ma; Jiande Lin; Shilin Cao (Biomass and Bioenergy, 2025)

Dynamic Task Allocation for Heterogeneous Multi-Autonomous Underwater Vehicle Collaboration Under Mine Countermeasures Missions - Juan Li; Baohua Liu; Caiyun Liu; Cong Lin (Journal of Marine Science and Engineering, 2025)
The task allocation of autonomous underwater vehicles (AUVs) is a crucial aspect of ocean exploration and mission execution tasks. In a mine countermeasures (MCM) combat scenario, when a new suspicious mission point is detected in the mission area, the heterogeneous multi-AUV system requires reallocation in real time. To address this, a soft time windows consensus-based bundle algorithm with partial reallocation (SWCBBA-PR) is designed. Based on the consensus-based bundle algorithm (CBBA), this algorithm comprehensively considers the underwater communication limitations and introduces the soft time window mechanism and partial reallocation mechanism. Its aim is to solve the partial reallocation problem that arises when new task points appear under the temporal-coupling constraints of complex underwater tasks. The SWCBBA-PR algorithm has been validated through simulation, demonstrating its ability to generate an optimal allocation scheme in the scenario of MCM mission emergence, and it exhibits good convergence performance.

Thiostrepton suppresses colorectal cancer progression through reactive oxygen species related endoplasmic reticulum stress - Zhexuan Li; Juan Nie; Runyu Zhou; Hui Huang; Xuemei Li; Li Wang; Lin Lv; Sichong Ren; Ming Zhao (Toxicology and Applied Pharmacology, 2025)

Bioactivity-guided isolation of potent inflammasome and mitochondria damage inhibitory diterpenoids from Orthosiphon wulfenioides - Wen-Chao Tu; Peng-Yun Yang; Xing-Jie Zhang; Yuan-Lin Kong; Bo Li; Hui-Juan Wang; Muhammad Aurang Zeb; Xiao-Li Li; Mei-Feng Liu; Wei-Lie Xiao (Phytochemistry, 2025)

Integrating lipidomics and metabolomics to reveal biomarkers of fat deposition in chicken meat - Wei Zhao; Jiahuan Hu; Lanlan Li; Lin Xue; Jinli Tian; Tong Zhang; Lijuan Yang; Yaling Gu; Juan Zhang (Food Chemistry, 2025)

Manganese halides with timely and delayed reversible thermal fluorescence quenching for dual-secure information encryption and anti-counterfeiting - Li Cong; Longyun Lv; Ying Liu; Yuxin Jia; Xuerui Chang; Yufan Lin; Juan Li; Bin-Bin Cui (Chemical Engineering Journal, 2025)

One new MOF with hierarchical pores achieving efficient one-step purifying C2H2, recycling CH4 and eliminating CO2 in C2H2 production - Lin Zhang; Ya-Li Bao; Rui-Cheng Gao; Wen-Juan Shi; Yi-Zhao Guo; Lei Hou; Yao-Yu Wang (Chemical Engineering Journal, 2025)

Combined application of Bacillus amyloliquefaciens and sodium selenite promotes tea seedling growth and selenium uptake by regulating the rhizosphere bacterial community - Liu Li; Lin Luo; Juan Zhan; Ali Raza; Chunying Yin (Biology and Fertility of Soils, 2025)

Pilot microbial electrolysis cell closes the hydrogen loop for hydrothermal wet waste conversion to jet fuel - Jinyue Jiang; Lin Du; Buchun Si; Harshal D. Kawale; Zixin Wang; Sabrina Summers; Juan A. Lopez-Ruiz; Shuyun Li; Yuanhui Zhang; Zhiyong Jason Ren (Water Research, 2025)

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

Fabrication of high-strength superhydrophobic aerogels via air-induced self-crosslinking for efficient oil-water separation - Fengfan Zhang; Zihao Yang; Xiaochen Li; Yaqing Hu; Kunyu Xu; Hongbo Wang; Meiqin Lin; Juan Zhang; Zhaoxia Dong (Fuel, 2025)

Preparation of nanocellulose-silk fibroin stiff hydrogel and high absorbing-low expansion xerogel via polysaccharide-protein interactions - Yue Ma; Tian Huang; Zhixing Hu; Juan Yu; Liang Liu; Lin Lin; Meijuan Chen; Ruoxian Jia; Xin Li; Zhiguo Wang; Yimin Fan (Carbohydrate Polymers, 2025)

Activation of protein kinase B rescues against thapsigargin-elicited cardiac dysfunction through regulation of NADPH oxidase and ferroptosis - Xiaohu Wang; Feng-Juan Li; Yong Cheng; Shuying Chen; Shuyi Zhu; Yingmei Zhang; Russel J. Reiter; Milad Ashrafizadeh; Jie Lin; Guizhen Wang; Ling Lin; Jun Ren (Chemico-Biological Interactions, 2025)

Plant litter crust enhances nitrogen accumulation by regulating microbial diversity and urease activity in semi-arid sandy soils - Zhen Cheng; Wei Liu; Zhigang Li; María José Carpio; Juan Carlos García-Gil; Zhanjun Wang; Gao-Lin Wu (Applied Soil Ecology, 2025)

Modification of gut and airway microbiota on ozone-induced airway inflammation - Fei Xu; Qiong Wu; Lin Yang; Han Sun; Juan Li; Zhen An; Huijun Li; Hui Wu; Jie Song; Wen Chen; Weidong Wu (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

A metabolic roadmap of waxy corn flavor - Jingyun Luo; Chunmei He; Shijuan Yan; Chenglin Jiang; An Chen; Kun Li; Yongli Zhu; Songtao Gui; Ning Yang; Yingjie Xiao; Shenshen Wu; Fajun Zhang; et al. (Molecular Plant, 2024)

Increased atmospheric thallium threats to populated areas: A mini review - Juan Liu; Yaole Huang; Yanyi Liu; Shunlong Jiang; Qiong Zhang; Pei Li; Ke Lin; Xuan Zeng; Haiyao Hu; Yang Cao; Xinni Xiong; Jin Wang (Journal of Hazardous Materials, 2024)

Effectiveness of composite fume suppression and deodorizing agents in improving performance and reducing emissions of rubber modified asphalt - Juan Xie; Zheyu Ding; Haochen Luo; Zhenzhen Lu; Shuaihui Li; Xucheng Zhao; Bin Huang; Jinmei Lin (Journal of Cleaner Production, 2024)

Comparative Analysis of Seven Endogenous Hormones in a Novel Dual-axillary Bud Mutant Genotype of Sugarcane - Kamal Priyananda Wickramasinghe; Jun Mao; Chao-hua Xu; Xiu-qin Lin; Xu-juan Li; Wei Qin; Hong-bo Liu; Xin-long Liu; Faisal Mehdi; Pei-fang Zhao; Xin Lu (Sugar Tech, 2024)
The sugarcane genotype YZ 07-86 is a distinct natural mutant with dual-axillary buds. Exploitation of this valuable trait in sugarcane breeding requires an understanding of the physiological mechanism of dual-axillary bud formation. This experiment determined the contents of indole-3-acetic acid (IAA), abscisic acid (ABA), gibberellins (GA 3 and GA 4 ), and three cytokinins (CKs), namely isopentenyl adenosine (iPA), zeatin riboside (ZR), and dihydrozeatin riboside (DHZR), in the shoot apical meristem tissues of YZ 07-86 and its sister line YZ 07-87, which served as the control genotype. The field experiment followed a completely randomized design with three replications for each genotype. Sampling was done at 5-day intervals, starting 106 days after planting. The ELISA technique was used to measure the contents of endogenous hormones. The study revealed that the mean contents of IAA, GA 3 , GA 4 , DHZR, and iPA were not significantly different ( P > 0.05) among the genotypes. Conversely, in YZ 07-86, the mean ZR content was significantly higher ( P < 0.05), and the mean ABA content was significantly lower than in the control genotype. Moreover, the mean content ratios of ZR/IAA, ZR/ABA, ZR/GA 3 , and ZR/GA 4 were also significantly higher in YZ 07-86. The study concludes that elevated ZR content and an increased ZR/ABA ratio directly contributes to dual-axillary bud formation in YZ 07-86, offering valuable insights for the advancement of sugarcane genotypes.

Transmission of carbapenem-resistant enterobacterales producing NDM-5 during the broiler breeding process in China - Ke Wu; Yuanyuan Zhang; Wei Xu; Xiaolong Lin; Cui Li; Juan Wang; Ruichao Li; Yizhi Tang; Changwei Lei; Hongning Wang (Veterinary Microbiology, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Simple theranostics nanoagent for precision suppression of tumor growth and metastasis: A traditional fermented product having a novel functional breakthrough - Pengmin Liu; Rong Dai; Juan Li; Lin Chen; Qi Liu; Yuhang Wang; Shichao Meng; Binyue Zhang; Jinxuan Li; Weiwei Kang; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2024)

A streamlined method to generate endothelial cells from human pluripotent stem cells via transient doxycycline-inducible ETV2 activation - Allen Chilun Luo; Jiuhai Wang; Kai Wang; Yonglin Zhu; Liyan Gong; Umji Lee; Xiang Li; Daniel M. Tremmel; Ruei-Zeng Lin; Donald E. Ingber; James Gorman; Juan M. Melero-Martin (Angiogenesis, 2024)

Inter‐algal associations and nutrients linked by Scenedesmus and Desmodesmus structure eukaryotic algal communities - Juan Lin; Hongxia Wang; Jianfeng Chen; Yun Li (Molecular Ecology, 2024)
Eutrophication reduces the variability of the community composition of plankton. However, the mechanisms underlying the diversity and restructuring of eukaryotic algal communities remain unknown. This study analysed the diversity and compositional patterns of algal communities in shallow eutrophic lakes. It investigated how these communities were modified by key genera through mediating inter‐algal associations under the influence of abiotic factors. Inter‐algal associations explained more variance in algal communities than environmental variables, and variation in composition and diversity was primarily derived from Scenedesmus , Desmodesmus and Cryptomonas , rather than nutrients. Scenedesmus and Desmodesmus were positively correlated with the genera of Chlorophyta and formed the hub of the algal association network. When the relative abundance of Scenedesmus and Desmodesmus increased from 0.41% to 13.74%, communities enriched in biomarkers of Bacillariophyta, Chrysophyceae and Cryptophyta transitioned to communities enriched in biomarkers of Chlorophyta. Moreover, negative associations between the Chlorophyta hub genera and other non‐Chlorophyta genera increased. High concentrations of total phosphorus altered the composition of algal communities by increasing the abundance of Scenedesmus and Desmodesmus , which in turn had cascading effects through inter‐algal associations. Additionally, algal communities with higher abundances of Scenedesmus and Desmodesmus were more susceptible to the effects of total phosphorus. Our study suggested that inter‐algal associations, centred on Scenedesmus and Desmodesmus , had a greater influence on algal diversity and community structure than other factors. Nutrient levels were not a direct driver of algal diversity and community structure adjustments, but acted indirectly by enhancing the influence of Scenedesmus and Desmodesmus .

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Heat acclimation alleviates the heat stress-induced impairment of vascular endothelial cells - Jirui Wen; Zhengdong Lin; Juan Cheng; Can Li; Ling Wang; Yuhao Zou; Xuehong Wan; Jifeng Liu; Jiang Wu (Tissue and Cell, 2024)

Abundant small microplastics hidden in water columns of the Yellow Sea and East China Sea: Distribution, transportation and potential risk - Jia Lin; Jia-Yuan Zheng; Zhi-Geng Zhan; Yuan-Ming Zhao; Qian-Zhi Zhou; Juan Peng; Yan Li; Xi Xiao; Jiang-Hai Wang (Journal of Hazardous Materials, 2024)

Environmental water-mediated dual-mechanism regulation of PtCuδ-MnOx-catalyzed acetone oxidation: Enhancement of MvK and inhibition of L-H mechanism - Lei Wang; Xin Zhang; Yonggang Sun; Yulong Ma; Min Xu; Juan Zhang; Yingbo Zhu; Li Zhu; Song Qiao; Jing Ma; Jinpeng Wei; Feng Lin (Journal of Environmental Chemical Engineering, 2024)

Genome sequencing analysis and validation of infestation-related functional genes of Vibrio parahaemolyticus LG2206 isolated from the hepatopancreas of diseased mud crab (Scylla paramamosain) in South China - Liu Guangxin; Liu Guangfeng; Li Ce; Ma Hongling; Deng Yiqin; Cheng Changhong; Jiang Jianjun; Fan Sigang; Feng Juan; Lin Li; Qin Zhendong; Guo Zhixun (Fish & Shellfish Immunology, 2024)

Pathogenesis-Related Protein 10 Family Genes Involved in Sugarcane Responses to Biotic Stressors and Salicylic Acid - Liang-Nian Xu; Xia-Ran Jiang; Jia-Xin Lin; Juan Li; Talha Javed; Jian-Ying Zhao; San-Ji Gao (Journal of Plant Growth Regulation, 2024)

Analysis of growth inhibition of continuously planted Casuarina equisetifolia in relation to characteristic soil microbial functions and nutrient cycling - Yu-Hua Wang; Lei Hong; Jian-Juan Li; Qing-Xu Zhang; Ai-Qi Wang; Shao-Xiong Lin; Ming-Yue Hu; Yi-Ling Chen; Wen-Xiong Lin; Hai-Bin Wang; Ze-Yan Wu (Applied Soil Ecology, 2024)

Bacterial diversity loss weakens community functional stability - Yu Guo; Juan Jin; Yuan Lu; Yixian Lin; Qi Liu; Zhefei Li (Applied Soil Ecology, 2024)

Mineralization and microbial utilization of poly(lactic acid) microplastic in soil - Yongxiang Yu; Shiying Lin; Binoy Sarkar; Juan Wang; Xinhui Liu; Danni Wang; Tida Ge; Yaying Li; Biao Zhu; Huaiying Yao (Journal of Hazardous Materials, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Enhancement of beneficial microbiomes in plant–soil continuums through organic fertilization: Insights into the composition and multifunctionality - Wen-Jing Li; Xin-Yuan Zhou; Xin-Li An; Li-Juan Li; Chen-Shuo Lin; Hua Li; Hong-Zhe Li (Soil Ecology Letters, 2024)

The role of Pleistocene dispersal in shaping species richness of sky island wintergreens from the Himalaya-Hengduan Mountains - Xiao-Juan Cheng; Peter W. Fritsch; Yan-Jun Lin; Guo-Hong Li; Yan-Quan Chen; Ming-Ying Zhang; Lu Lu (Molecular Phylogenetics and Evolution, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Electrothermal-assisted all-weather solar steam generator based on hydrogel implantation strategy - Hao Fang; Jialiang Ma; Jing Lin; Juan Du; Shikuo Li; Hui Zhang; Fangzhi Huang (Chemical Engineering Journal, 2024)

Two-photon polymerization-based 3D micro-scaffolds toward biomedical devices - Wei Wang; Zi-Qing Chen; Bin Lin; Mei-Chen Liu; Yang Zhang; Shu-Juan Liu; Yang Li; Qiang Zhao (Chemical Engineering Journal, 2024)

Inhibition of ER stress using tauroursodeoxycholic acid rescues obesity-evoked cardiac remodeling and contractile anomalies through regulation of ferroptosis - Feng-Juan Li; Miyesaier Abudureyimu; Zeng-Hui Zhang; Jun Tao; Asli F. Ceylan; Jie Lin; Wei Yu; Russel J. Reiter; Milad Ashrafizadeh; Jun Guo; Jun Ren (Chemico-Biological Interactions, 2024)

Alleviating Pentatrichomonas hominis-induced damage in IPEC-J2 cells: the beneficial influence of porcine-derived lactobacilli - Yibin Zhu; Haiming Cai; Zhuanqiang Yan; Hanqin Shen; Siyun Fang; Dingai Wang; Shenquan Liao; Nanshan Qi; Minna Lv; Xuhui Lin; Junjing Hu; Yongle Song; et al. (Veterinary Research Communications, 2024)

Synthesis of metal-free benzimidazole-based catalysts and its application in CO2 cycloaddition - Li Lin; Huigui Yang; Shuangjiang Li; Yi Liu; Yunfei Zhi; Shaoyun Shan; Juan Xu (Environmental Science and Pollution Research, 2024)

Multifaceted leaf litter traits shape soil fauna communities: Evidence from subtropical monocultural plantations - Dangjun Wang; Wuyang Xie; Xiaoyuan Lin; Fan Li; Chaochao Deng; Xiangyu Zeng; Kuo Tan; Yiping Yuan; Zhirong Gu; Mingxi Jiang; Zhun Mao; Juan Zuo (Forest Ecology and Management, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Optimized design of quaternary amino-functionalized chitosan fibers for ultra-high diclofenac adsorption from wastewater - Xiaoyu Lin; Myung-Hee Song; Wenhao Li; Wei Wei; Xiaohui Wu; Juan Mao; Yeoung-Sang Yun (Chemosphere, 2024)

Source-sink relationships of anthropogenic metal(loid)s from urban catchment to waterway in relation to spatial pattern of urban green infrastructures - Juan Li; Linlin Zhang; Shen Yu; Bing Hong; Ruihan Lin; Qi Li; Haifeng Jia; Dawen Yang; Chengwei Gu; Qimeng Jia (Journal of Hazardous Materials, 2024)

An improved process for removal and recovery of heavy petroleum from solids using a ferrate-based hybrid oxidant - Yurou Guo; Peng Lv; Juan Li; Changqing He; Lin He; Hong Sui (Environmental Research, 2024)

Environmental DNA metabarcoding reveals fish diversity, community assembly and one invasive species prevalence in a National Park of Liaohe in September - Ni Xin; Zhao Li; Yong-Wei Jiang; Hui Wang; Juan Tan; Yang Li; Bing-Jiao Sun; Xiao-Long Lin (Frontiers in Marine Science, 2024)
The escalating environmental changes are imposing multiple pressures on biodiversity conservation, thereby, more attention has been paid to fish diversity and community assembly patterns. Fish diversity in Liaohe River has deteriorated significantly due to overfishing, environmental pollution and other reasons, in addition, no fish survey related research has been published in Liaohe National Park in recent years. In order to study the diversity of fish species in the area and to investigate the presence of any invasive species. This study used eDNA metabarcoding to explore the distribution and diversity of fish communities in the Liaohe National Park. The study showed that a total of 54 species of fish from six orders, 14 families, and 39 genera were detected, meantime, the invasive species Lepomis cyanellus was found at two sampling sites. The α-diversity results showed that estuarine sites had the highest species diversity. The spatial structure of fish communities in the upstream and downstream reaches were similar as indicated by non-metric multidimensional scaling. In our study, the fish community is influenced by both deterministic and stochastic processes, with the stochastic processes being the main factor. The potential existence of L. cyanellus in Liaohe National Park might be resulted from aquaculture, ornamental pet trade, other economic fish farming, artificial release. The relatively low number of fish species in this study may be attributed to the limited number of sampling events and sampling sites. In addition to these factors, over exploitation of resources, water pollution, and the invasion of alien species have directly impacted the biodiversity of aquatic life. The results of this study lay a foundation for the future biodiversity investigation in National Parks of China, meantime, the use of eDNA monitoring is crucial to prevent, to control and limit the spreading of invasive species in advance.

Performance on adsorption of toluene by ionic liquid-modified AC in high-humidity exhaust gas - Ji-feng Guo; Zhao-li Ping; Nan Liu; Xin Zhang; Jia-lin Lv; Yan-yan Yao; Jia-jun Hu; Wen-juan Wang; Ji-xiang Li (Environmental Science and Pollution Research, 2024)

Ferrocene-functionalized zirconium-oxo clusters for achieving high-performance thermocatalytic redox reactions - Su-Juan Yao; Jiao-Min Lin; Long-Zhang Dong; Ying-Lin Li; Ning Li; Jiang Liu; Ya-Qian Lan (Science Bulletin, 2024)

Microplastics in remote coral reef environments of the Xisha Islands in the South China Sea: Source, accumulation and potential risk - Jia Lin; Yuan-Ming Zhao; Zhi-Geng Zhan; Jia-Yuan Zheng; Qian-Zhi Zhou; Juan Peng; Yan Li; Xi Xiao; Jiang-Hai Wang (Journal of Hazardous Materials, 2024)

A CRISPR/Cas12a-assisted bacteria quantification platform combined with magnetic covalent organic frameworks and hybridization chain reaction - Xuening Shi; Hang Li; Shuo Yao; Yukun Ding; Xiuzhu Lin; Hui Xu; Yi Liu; Chao Zhao; Tong Zhang; Juan Wang (Food Chemistry, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Two new monoterpene esters from Illigera paviflora Dunn roots - Meng-Yuan Jiang; Xiao-Yun Pu; Wen-Ting Li; Juan Liu; Xiao-Li Zeng; Hong-Rui Li; Xi-Shan Bai; Lin Hu; Xiang-Zhong Huang (Natural Product Research, 2024)

The emerging role of zinc on alleviating inflammatory responses and enhancing immunity in grass carp (Ctenopharyngodon idella) - Xin Zeng; Zheng-Xing Song; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Juan Yang; Lin Feng (Aquaculture, 2024)

Immunoprotective effects of DNA vaccine against Eimeria tenella based on EtAMA3 and EtRON2L2 - Xiangjie Chen; Xixi Qiu; Junli Ni; Shenquan Liao; Nanshan Qi; Juan Li; Minna Lv; Xuhui Lin; Haiming Cai; Junjing Hu; Yongle Song; Lijun Yin; et al. (Veterinary Parasitology, 2024)

PM2.5-induced premature senescence in HUVECs through the SIRT1/PGC-1α/SIRT3 pathway - Qing Yan; Rao Zheng; Yi Li; Juan Hu; Meidi Gong; Manman Lin; Xuecong Xu; Jing Wu; Shikun Sun (Science of The Total Environment, 2024)

The association between per-/polyfluoroalkyl substances in serum and thyroid function parameters: A cross-sectional study on teenagers living near a Chinese fluorochemical industrial plant - Lin-Na Xie; Xiao-Chen Wang; Li-Qin Su; Sai-Sai Ji; Wen Gu; Holly Barrett; Xiao-Jie Dong; Hui-Juan Zhu; Sha-Sha Hou; Zhen-Huan Li; Yi-Lin Liu; Ling Zhang; et al. (Science of The Total Environment, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Multi-object detection and behavior tracking of sea cucumbers with skin ulceration syndrome based on deep learning - Fengli Ge; Kui Xuan; Peng Lou; Juan Li; Lingxu Jiang; Jiasheng Wang; Qi Lin (Frontiers in Marine Science, 2024)
Skin ulceration syndrome of sea cucumbers is one of the most serious diseases in intensive aquaculture, and it is the most effective way of preventing the spread of this disease to detect the abnormal behavior of sea cucumbers in time and take corresponding measures. However, the detection and tracking of multi-object is a hard problem in sea cucumber behavior analysis. To solve this problem, this paper first proposes a novel one-stage algorithm SUS-YOLOv5 for multi-object detection and tracking of sea cucumbers. The proposed SUS-YOLOv5 optimizes the maximum suppression algorithm in the overlapping region of the object detection box. Next, the SE-BiFPN feature fusion structure is proposed to enhance the transmission efficiency of feature information between deep and shallow layers of the network. Then, a MO-Tracking algorithm is proposed integrated with DeepSORT to achieve real-time multi-object tracking. Experimental results show that the mAP @0.5 and mAP @0.5:0.95 of the proposed object detector reach 95.40% and 83.80%, respectively, which are 3.30% and 4.10% higher than the original YOLOv5s. Compared with the traditional SSD, YOLOv3, and YOLOv4, the mAP of SUS-YOLOv5 is improved by 5.49%, 1.57%, and 3.76%, respectively. This research can realize the multi-object detection and tracking, which lays the foundation for the prediction of skin ulceration syndrome in sea cucumbers and has a certain practical application value for improving the intelligence level of aquaculture.

New solution for predicting the removal efficiency of organic contaminants by UV/ H2O2: From a case study of 1H-benzotriazole - Juan Dang; Ling Lin; Li-ao Gao; Lin Qi; Shi-bo Zhang; Qing-zhu Zhang; Shuai Tian (Science of The Total Environment, 2024)

Nanoplastic propels diet-induced NAFL to NASH via ER-mitochondrial tether-controlled redox switch - Jie Wei; Jintao Liu; Huan Wang; Kai Wen; Xiuye Ni; Yilong Lin; Jingru Huang; Xiang You; Zhao Lei; Juan Li; Heqing Shen; Yi Lin (Journal of Hazardous Materials, 2024)

Influence on the volatilization of ethyl esters: Nonnegligible role of long-chain fatty acids on Baijiu flavor via intermolecular interaction - Qing-Ru Liu; Xian-Li Lin; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Xiao-Juan Zhang; Zheng-Hong Xu (Food Chemistry, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Physiology, microcystin production, and transcriptomic responses of Microcystis aeruginosa exposed to calcium and magnesium - Li Yin; Lin Xu; Kaipian Shi; Weiyu Chen; Yong Zhang; Juan Wang; Junfeng An; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Science of The Total Environment, 2024)

RETRACTED: Applying thallium isotopic compositions as novel and sensitive proxy for Tl(I)/Tl(III) transformation and source apportionment - Juan Liu; Lulu Wang; Jingfen Lin; Wenhuan Yuan; Liangzhong Li; Yung-Kang Peng; Xinni Xiong; Huimin Cao; Xudong Wei; Qi'en Ouyang; Holger Lippold; Jin Wang; et al. (Science of The Total Environment, 2024)

Long-term efficacy and safety of leflunomide combined with low-dose prednisone in treatment of myasthenia gravis: a retrospective study - Li Qiu; Pei Chen; Changyi Ou; Juan Deng; Zhidong Huang; Zhongqiang Lin; Qian Ma; Xin Huang; Lu Yu; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Three new cardenolides from the fruits of Cascabela thevetia (L.) Lippold and their cytotoxic activities - Juan Long; Jia-Cheng Ouyang; Yu-Hao Luo; Qi-Jing Wu; Xiao-Tong Liao; Zhi-Le Chen; Qi-Lin Wang; Xiao-Yan Liang; Li Liu; Xue-Mei Yang; Xiao-San Li (Natural Product Research, 2024)

A new C 19 -diterpenoid alkaloid in Aconitum georgei Comber - Lin-Lin Yao; Sheng-Qi Zhang; Ce Guo; Bin-Xian Li; Hua-Juan Yang; Tian-Peng Yin; Le Cai (Natural Product Research, 2024)

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Study on the supercooling and crystallization mechanism of saline soil based on thermodynamic framework - Kunyu Li; Chong Wang; Yumo Wu; Zhikun Lin; Junping Ren; Juan Gao; Shuangyang Li (Journal of Hydrology, 2024)

Development of a two-dimensional model to assess carbon dynamics and anthropogenic effects on CO2 emissions in the Tan river, southern China - Zhonghan Chen; Qiuyan Li; Shibo Yan; Juan Xu; Qiaoyun Lin; Zhuangming Zhao; Ziying He (Journal of Environmental Management, 2024)

Gaseous signaling molecule H2S as a multitasking signal molecule in ROS metabolism of Oryza sativa under thiocyanate (SCN−) pollution - Yu-Xi Feng; Peng Tian; Yu-Juan Lin; Dan-Yang Cao; Cheng-Zhi Li; Abid Ullah (Environmental Pollution, 2024)

Experimental and numerical investigation of the expansion mechanism of beam-end expansion devices in large-span bridge - Tao Liao; Juan Song; Jun Lai; Kai Wang; Ping Wang; Zhiheng Li; Jingmang Xu; Yao Qian; Junke Lin (Engineering Structures, 2024)

Blue polyimides for high-performance solution-processable organic light-emitting diodes - Wenhui Wang; Kaijin Chen; Chuying Li; Faxu Lin; Yuxuan Li; Yubo Long; Juan Zhao; Siwei Liu; Zhenguo Chi; Jiarui Xu; Yi Zhang; Yuguang Ma (Chemical Engineering Journal, 2024)

AMPKα is active in autophagy of endothelial cells in arsenic-induced vascular endothelial dysfunction by regulating mTORC1/p70S6K/ULK1 - Ziqi Xu; Qiaoling Liu; Jinyu Li; Jingqiu Wang; Zhihan Yang; Juan Wang; Lin Gao; Jin Cheng; Jing He; Yishan Dong; Xiangnan Guo; Jing Cui; et al. (Chemico-Biological Interactions, 2024)

Eudesmane-type sesquiterpenoids from the aerial parts of Artemisia lavandulaefolia and their anti-pancreatic cancer activities - Lin-Fen Ding; Guo-Xian Hu; Yu-Yao Liu; Qiu-Hua Wang; Zhang-Juan Li; Meng-Xia Shen; Gui-Fa Zhu; Xing-De Wu; Jia Su (Phytochemistry, 2023)

Limonoids from the roots of Melia azedarach and their anti-inflammatory activity - Min Song; Hui-Juan Luo; Zi-Wei Li; Ling Qiu; Yu-Xin Zhao; Cheng-Wei He; Xiao-Qi Zhang; Wen-Cai Ye; Li-Gen Lin; Qing-Wen Zhang (Phytochemistry, 2023)

Application of engineered heme enzymes based on myoglobin with high peroxidase activity for efficient degradation of various emerging pollutants - Guang-Rong Wu; Jia-Kun Xu; Li-Juan Sun; Ying-Fu Li; Shu-Qin Gao; Ying-Wu Lin (Journal of Environmental Chemical Engineering, 2023)

pH-Responsive graphene oxide/poly (methacrylic acid) hybrid nanofiltration membrane performance for water treatment - Li-yue Sun; De-hao Yu; Zhao-ge Juan; Yao Wang; Yan-xin Wang; Matt J. Kipper; Lin-jun Huang; Jian-guo Tang (Journal of Environmental Chemical Engineering, 2023)

Anti-complement factor H (CFH) autoantibodies could delay pristane-induced lupus nephritis - Lin-Lin Li; Zhong-qiu Luan; Ying Tan; Hui Wang; Xiao-Juan Yu; Zhen Qu; Feng Yu; Min Chen (Immunologic Research, 2023)
Purpose Anti-complement factor H (CFH) autoantibodies could be detected in lupus and its significance remained to be elucidated. Herein, we aimed to explore the roles of anti-CFH autoantibodies based on pristane-induced lupus mice. Methods Twenty-four female Balb/c mice were randomly divided into four groups, with one group injected with pristane (pristane group), one group with pristane and then human CFH (hCFH) (pristane-CFH group) 3 times, and the other two as vertical controls, PBS group and PBS-CFH group. Histopathological analysis was performed six months after pristane administration. Levels of hCFH, anti-CFH autoantibodies and anti-dsDNA antibody were detected. Murine IgG (mIgG) were purified and cross-reactivity, epitopes, subclasses and functional analysis were further evaluated in vitro. Results Immunization with hCFH and subsequent development of anti-CFH autoantibodies significantly attenuated nephritis of pristane-induced lupus, including lower levels of urinary protein and serum creatinine, decreased levels of serum anti-dsDNA antibody, greatly ameliorated renal histopathologic damage, decreased IgG, complements (C1q, C3) deposits and lower inflammatory factor (IL-6) expression in glomerulus. Furthermore, the purified mIgG (contained anti-CFH autoantibodies) could recognize both hCFH and murine CFH, and the epitopes were predominantly located in hCFH short consensus repeats (SCRs) 1–4, 7 and 11–14. The IgG subclasses were predominant IgG1. The autoantibodies could enhance the binding between hCFH and C3b, and increase factor I mediated-C3b lysis in vitro. Conclusion Our results suggested that anti-CFH autoantibodies could attenuate pristane-induced lupus nephritis by increasing bio-functions of CFH on regulating complement activation and controlling inflammation.

Peptidomic Analysis and Potential Bioactive Peptides Identification Targeting Endometrial Cancer - Hanzi Xu; Shenglong Yuan; Lin Zhou; Huixin Li; Juan Lv; Xiaoyan Shi; Wangfei Wu; Zhijian Feng; Zhen Gong (International Journal of Peptide Research and Therapeutics, 2023)

The R2R3-MYB transcription factor CsMYB42 regulates theanine biosynthesis in albino tea leaves - Nianci Xie; Xiangxiang Huang; Jiaxin Zhou; Xiaofeng Song; Junming Lin; Meihong Yan; Mingzhi Zhu; Juan Li; Kunbo Wang (Plant Science, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Hybrid chain reaction and selective recognition-based homogeneous dual-fluorescence analysis of circulating tumor cells in clinical ovarian cancer samples - Qian Hu; Dan Tang; Mei Li; Xiaodu Liang; Juan Zhou; Yanming Meng; Yinhao Wei; Shixin Yan; Ruoyu Lin; Xiaoyu Niu; Lin Zhang (Analytica Chimica Acta, 2023)

Movement of protistan trophic groups in soil–plant continuums - Chenshuo Lin; Wen‐Jing Li; Li‐Juan Li; Roy Neilson; Xin‐Li An; Yong‐Guan Zhu (Environmental Microbiology, 2023)
Protists, functionally divided into consumers, phototrophs, and parasites act as integral components and vital regulators of microbiomes in soil–plant continuums. However, the drivers of community structure, assembly mechanisms, co‐occurrence patterns, and the associations with human pathogens and different protistan trophic groups remain unknown. Here, we characterized the phyllosphere and soil protistan communities associated with three vegetables under different fertilization treatments (none and organic fertilization) at five growth stages. In this study, consumers were the most diverse soil protist group, had the role of inter‐kingdom connector, and were the primary biomarker for rhizosphere soils which were subjected to decreasing deterministic processes during plant growth. In contrast, phototrophs had the greatest niche breadth and formed soil protistan hubs, and were the primary biomarkers for both bulk soils and the phyllosphere. Parasites had minimal input to microbial co‐occurrence networks. Organic fertilization increased the relative abundance (RA) of pathogenic protists and the number of pathogen–consumer connections in rhizosphere soils but decreased protistan richness and the number of internal protistan links. This study advances our understanding of the ecological roles and potential links between human pathogens and protistan trophic groups associated with soil–plant continuums, which is fundamental to the regulation of soil–plant microbiomes and maintenance of environmental and human health.

Proteomics reveals the underlying mechanism by which the first uneven division affects embryonic development in pig - Fuquan Zhu; Xinyue Lu; Yuan Jiang; Dayu Wang; Linqing Pan; Chao Jia; Lin Zhang; Yan Xie; Mingyue Zhao; Huijun Liu; Meixia Wang; Tingzhang Wang; et al. (Theriogenology, 2023)

Preparation of natural complex waxy structure for the evaluation of preservation performance of blueberry - Xuedong Gu; Juan Li; Lin Yang; Lei Liu; Lan Xiao (Food Bioscience, 2023)

Fabrication of organic P-N aerogel towards simultaneously super thermal insulation, enhanced compressive strength, flame retardancy and smoke suppression for the rigid polyurethane foam - Ying-Ming Li; Wen-Juan Hu; Shuang-Lin Hu; Yi-Ran Li; De-Yi Wang (Chemical Engineering Journal, 2023)

Breaking the dilemma of low selectivity in the oxidative coupling of methane over Mn-Na2WO4/SiO2 at low temperatures - Lin Xu; Anna Zanina; Kai Wu; Jianshu Li; Juan Chen; Yuming Li; Guiyuan Jiang; Evgenii V. Kondratenko (Chemical Engineering Journal, 2023)

Performance enhancement of integrating microbial electrolysis cell on two-stage anaerobic digestion of food waste: Electro-methanogenic stage versus electro-two stages - Tianlong Zheng; Chunlin Bian; Benyi Xiao; Xiangyu Chen; Juan Wang; Lin Li (Bioresource Technology, 2023)

Efficient synthesis of 2’-deoxyguanosine in one-pot cascade by employing an engineered purine nucleoside phosphorylase from Brevibacterium acetylicum - Lian Xu; Hui-Min Li; Juan Lin (World Journal of Microbiology and Biotechnology, 2023)

NRF2 Antagonizes HIV-1 Tat and Methamphetamine-Induced BV2 Cell Ferroptosis by Regulating SLC7A11 - Shucheng Lin; Hao Cheng; Genmeng Yang; Chan Wang; Chi-Kwan Leung; Shuwei Zhang; Yi Tan; Huijie Zhang; Haowei Wang; Lin Miao; Yi Li; Yizhen Huang; et al. (Neurotoxicity Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Simultaneous biohythane and volatile fatty acids production from food waste in microbial electrolysis cell-assisted acidogenic reactor - Chunlin Bian; Xiangyu Chen; Juan Wang; Benyi Xiao; Rongzhan Liu; Lin Li; Jianguo Liu (Journal of Cleaner Production, 2023)

Transcriptome analysis reveals important regulatory genes and pathways for tuber color variation in Pinellia ternata (Thunb.) Breit - Cong Yin; Ding Tang; Xiaoyu Liu; Zihan Li; Yulin Xiang; Kaiming Gao; Heyu Li; Lin Yuan; Bisheng Huang; Juan Li (Protoplasma, 2023)

Involvement of IGF1 in endoplasmic reticulum stress contributes to cataract formation through regulating Nrf2/NF-κB signaling - Ruiping Peng; Hongmei Lin; Haocheng Zhu; Yi Zhang; Tiancheng Bao; Weili Li; Juan Deng (Functional & Integrative Genomics, 2023)

Seasonal–interannual–decadal variations of sea level in the South China Sea and connections with the tropical–subtropical Pacific - Juan Li; Wei Tan; Wenjin Sun; Lina Yang; Lei Lin; Qingjun Fu (International Journal of Climatology, 2023)
Different timescale contributions to the sea‐level variation in the South China Sea (SCS) are evaluated in this paper. On seasonal timescale, the large variance of the sea‐level anomaly (SLA) could account for more than 70% of the monthly sea‐level variation in the western shallow continental shelf and the area of Luzon cold eddy. Besides, the seasonal explained variance percentage (skill) has 2 weak centres (50%–70%) off eastern Vietnam, which is related to the summertime eddy pair in the SCS. On interannual‐to‐decadal (low‐frequency) timescale, the skill has two large‐value regions (Zone A and Zone B). Zone A is characterized by double centres off eastern Vietnam, but the meridional position of the double centres is farther north than that of the eddy pair. The skill in Zone A is in the range of 35%–55%, and about 50%–70% of the low‐frequency variation comes from the steric effect. Zone B is off the west coast of the Philippines. The skill in Zone B increases southward, and it is dominated by the wind‐induced dynamic process which is attributed to the remote Rossby wave from the tropical Pacific. Based on the S‐EOF analysis, the SEOF‐1 mode mainly portrays the decadal variation of the SLA, while the SEOF‐2 mode reflects the interannual variation of the SLA. In Zone B, almost all of the low‐frequency variation could be attributed to ENSO and PDO, especially to PDO which has a larger contribution. However, the double centres in Zone A are governed by the SCS summer monsoon, instead of ENSO and PDO.

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

A sandwiched photoelectrochemical sensor for high-throughput single-cell analysis based on low-toxic and near-infrared AgInS2 microarray - Lin Zhong; Kejun Guo; Su Li; Juan Wang (Chemical Engineering Journal, 2023)

A spike-trimer protein-based tetravalent COVID-19 vaccine elicits enhanced breadth of neutralization against SARS-CoV-2 Omicron subvariants and other variants - Rui Wang; Hongpeng Huang; Chulin Yu; Chunyun Sun; Juan Ma; Desheng Kong; Yalong Lin; Dandan Zhao; Shaozheng Zhou; Jianbo Lu; Sai Cao; Yanjing Zhang; et al. (Science China Life Sciences, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

A novel fluorescent probe for imaging endogenous hydrogen sulfide in living cells and mice models of acute liver injury - Kai Wang; Rui Guo; Xu-Yang Chen; Xiu-Lin Li; Zhi-Gang Hu; Xiao Wang; Chao-Yue Wang; Ya-Juan Qin; Kun Yao; Yu-Shun Yang (Chemical Engineering Journal, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Effect of lignocellulose/montmorillonite immobilized Bacillus sp. on monosodium glutamate wastewater - Bai-Yun Zhao; Xiao-Kai Liu; Xi-Lin Li; Li-Juan Zhou; Li Wang (Environmental Science and Pollution Research, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Corrigendum to “Mechanism of PM2.5-induced human bronchial epithelial cell toxicity in central China” [J Hazard Mater 396 (2020) 122747] - Shuyin Duan; Meihua Zhang; Yaqiong Sun; Zhenya Fang; Hefeng Wang; Shuxian Li; Yanze Peng; Juan Li; Junxia Li; Jiaqi Tian; Haoyu Yin; Sanqiao Yao; et al. (Journal of Hazardous Materials, 2023)

Shape-Controlled synthesis of conjugated microporous polymer nanotubes and their implementation in continuous flow polymerization - Xue Li; Xi Juan Zhang; Wan Lin Guo; Yuan Huang; Tao Cai (Chemical Engineering Journal, 2023)

Three-dimensional quantitative structural-activity relationship and molecular dynamics study of multivariate substituted 4-oxyquinazoline HDAC6 inhibitors - Linan Zhao; Le Fu; Guangping Li; Yongxin Yu; Juan Wang; Haoran Liang; Mao Shu; Zhihua Lin; Yuanqiang Wang (Molecular Diversity, 2023)

Transcriptome analysis reveals the regulatory effects of Bacillus amyloliquefaciens and Bacillus pumilus on immune and digestive related genes in the spleen of weanling black goats - Nanchi Zhang; Juan Li; Li Wang; Yong Wei; Quzhe Emu; Feng Xu; Lin Zhang (Functional & Integrative Genomics, 2023)

An Assessment of Marine Heatwaves in a Global Eddy-Resolving Ocean Forecast System: A Case Study around China - Yiwen Li; Juan Liu; Pengfei Lin; Hailong Liu; Zipeng Yu; Weipeng Zheng; Jinlei Chen (Journal of Marine Science and Engineering, 2023)
Marine heatwaves (MHWs) are becoming increasingly frequent and intense around China, impacting marine ecosystems and coastal communities. Accurate forecasting of MHWs is crucial for their management and mitigation. In this study, we assess the forecasting ability of the global eddy-resolving ocean forecast system LICOM Forecast System (LFS) for the MHW events in October 2021 around China. Our results show that the 1-day lead forecast by the LFS accounts for up to 79% of the observed MHWs, with the highest skill during the initial and decay periods. The forecasted duration and intensity of the MHW event are consistent with observations but with some deviations in specific regions of the Yellow and South China seas. A detailed analysis of the heat budget reveals that the forecasted shortwave radiation flux is a key factor in the accuracy of the forecasted MHW duration and intensity. The oceanic dynamic term also greatly contributes to the accuracy in the southern Yellow Sea. In addition, the increasing bias of the forecasted duration and intensity with lead time are mainly caused by the underestimated shortwave radiation. Our findings suggest that improving the accuracy of oceanic dynamic processes and surface radiation fluxes in the LFS could be a promising direction to enhance the forecasting ability of marine extreme events such as MHWs.

Click-crosslinked in-situ hydrogel improves the therapeutic effect in wound infections through antibacterial, antioxidant and anti-inflammatory activities - Xiong-Xin Lei; Chen-Yu Zou; Juan-Juan Hu; Yan-Lin Jiang; Xiu-Zhen Zhang; Long-Mei Zhao; Tao He; Qing-Yi Zhang; Ya-Xing Li; Jesse Li-Ling; Hui-Qi Xie (Chemical Engineering Journal, 2023)

Environmentally-friendly biorecovery of manganese from electrolytic manganese residue using a novel Penicillium oxalicum strain Z6-5-1: Kinetics and mechanism - Shuai Zhao; Bo-Wen Zheng; Yu-Cang Wang; Fei He; Li-Juan Wang; Xiong Lin; Xue-Mei Luo; Jia-Xun Feng (Journal of Hazardous Materials, 2023)

Stability of potentially toxic elements in municipal sludge biochars modified by MgCl2 and phosphate - Qiqi Huang; Siqi Chen; Jinhao Lin; Jingzi Beiyuan; Jin Wang; Juan Liu; Yundang Wu; Xiaolian Wu; Fuhua Li; Wenbing Yuan; Chengrong Nie (Waste Disposal & Sustainable Energy, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Spatial effects of urban green infrastructure on instream water quality assessed by chemical and sensory indicators - Juan Li; Shen Yu; Bing Hong; Ruihan Lin; Qi Li; Linlin Zhang; Tao Lin; Haifeng Jia; Dawen Yang; Chengwei Gu; Qimeng Jia (Science of The Total Environment, 2023)

Construction of the dynamic model of SCI rehabilitation using bidirectional stimulation and its application in rehabilitating with BCI - Zhengzhe Cui; Juan Lin; Xiangxiang Fu; Shiwei Zhang; Peng Li; Xixi Wu; Xue Wang; Weidong Chen; Shiqiang Zhu; Yongqiang Li (Cognitive Neurodynamics, 2023)

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

Water microecology is affected by seasons but not sediments: A spatiotemporal dynamics survey of bacterial community composition in Lake Changshou—The largest artificial lake in southwest China - Ai-ling Chen; Fu-qing Xu; Xia Su; Fu-pan Zhang; Wan-chao Tian; Shang-jie Chen; Fang Gou; Zhi-lin Xing; Jin-xin Xiang; Juan Li; Tian-tao Zhao (Marine Pollution Bulletin, 2023)

A combined study on Vallisneria spiralis and lanthanum modified bentonite to immobilize arsenic in sediments - Wenming Yan; Xiangyu He; Tingfeng Wu; Musong Chen; Juan Lin; Xiang Chen; Qi Li; Minjuan Li; Yulin Yan; Qi Yao (Environmental Research, 2023)

Recycle waste washcloth to design Fe3O4/FeS2/C heterojunction membrane as high-area capacity freestanding anode for sodium-ion batteries - Qing Lin; Shaocheng Zhang; Li-Juan Yu; Baoxiu Hou; Shuaihua Zhang; Zheng Wang; Jianjun Song; Xiaoxian Zhao (Chemical Engineering Journal, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

Selenium attenuates the association of co-exposure to arsenic, cadmium, and lead with cognitive function among Chinese community-dwelling older adults - Bei-Jing Cheng; Jie Sheng; Hong-Li Wang; Yuan Wang; Hong-Juan Cao; Xiu-De Li; Ting-Ting Zhou; Xiang-Long Meng; Huan-Huan Nie; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; et al. (Environmental Science and Pollution Research, 2022)

Effects of exposure to phthalate during early pregnancy on gestational diabetes mellitus: a nested case–control study with propensity score matching - Wei Chen; Caidie He; Xiang Liu; Songlin An; Xia Wang; Lin Tao; Haonan Zhang; Yingkuan Tian; Nian Wu; Pei Xu; Dengqing Liao; Juan Liao; et al. (Environmental Science and Pollution Research, 2022)

The association between essential trace element mixture and atherosclerotic cardiovascular disease risk among Chinese community-dwelling older adults - Xiang-long Meng; Yuan Wang; Hong-li Wang; Huan-huan Nie; Bei-jing Cheng; Hong-juan Cao; Xiu-de Li; Su-fang Wang; Gui-mei Chen; Fang-biao Tao; Jie Sheng; Lin-sheng Yang (Environmental Science and Pollution Research, 2022)

First report of leaf blight on Panax notoginseng caused by Pestalotiopsis trachycarpicola in China - Cheng Zhong Lan; Xiong Lin; Yu Li Dai; Lin Gan; Xiao Fei Liu; Hong Chun Ruan; Xiu Juan Yang (Journal of Plant Pathology, 2022)

Identification of a 5-gene-risk score model for predicting luminal A-invasive lobular breast cancer survival - Yi-Huan Chen; Tao-Feng Zhang; Yi-Yuan Liu; Jie-Hua Zheng; Wei-Xun Lin; Yao-Kun Chen; Jie-Hui Cai; Juan Zou; Zhi-Yang Li (Genetica, 2022)

Ancylostoma ceylanicum Infection in a Miniature Schnauzer Dog Breed - Xu-Hui Lin; Hai-Ming Cai; Zhuan-Qiang Yan; Shen-Quan Liao; Min-Na Lv; Cai-Yan Wu; Juan Li; Jun-Jing Hu; Wen-Wan Xiao; Jian-Fei Zhang; Nan-Shan Qi; Ming-Fei Sun (Acta Parasitologica, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Multitrophic diversity and biotic associations influence subalpine forest ecosystem multifunctionality - Ya‐Huang Luo; Marc W. Cadotte; Jie Liu; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Jia‐Yun Zou; Zhong‐Zheng Chen; Xue‐Long Jiang; Juan Li; Kun Xu; De‐Zhu Li; et al. (Ecology, 2022)
Biodiversity across multiple trophic levels is required to maintain multiple ecosystem functions. Yet it remains unclear how multitrophic diversity and species interactions regulate ecosystem multifunctionality. Here, combining data from 9 different trophic groups (including trees, shrubs, herbs, leaf mites, small mammals, bacteria, pathogenic fungi, saprophytic fungi, and symbiotic fungi) and 13 ecosystem functions related to supporting, provisioning, and regulating services, we used a multitrophic perspective to evaluate the effects of elevation, diversity, and network complexity on scale‐dependent subalpine forest multifunctionality. Our results demonstrated that elevation and soil pH significantly modified species composition and richness across multitrophic groups and influenced multiple functions simultaneously. We present evidence that species richness across multiple trophic groups had stronger effects on multifunctionality than species richness at any single trophic level. Moreover, biotic associations, indicating the complexity of trophic networks, were positively associated with multifunctionality. The relative effects of diversity on multifunctionality increased at the scale of the larger community compared to a scale accounting for neighboring interactions. Our results highlight the paramount importance of scale‐ and context‐dependent multitrophic diversity and interactions for a better understanding of mountain ecosystem multifunctionality in a changing world.

Intrauterine hyperglycemia impairs endometrial receptivity via up-regulating SGK1 in diabetes - Haiyan Xu; Jingyi Li; Luyang Jin; Dan Zhang; Bin Chen; Xinmei Liu; Xianhua Lin; Yiting Huang; Zhanghong Ke; Juan Liu; Lin Gao; Jianzhong Sheng; et al. (Science China Life Sciences, 2022)

Correction to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2022)

Sesquiterpene lactones from Carpesium abrotanoides L. and their activity in inducing protective autophagy - Bao-Jia Yang; Juan Wang; Zheng-Quan Zeng; Xu Yang; Ai-Ying Huang; Xiao-Jiang Hao; Xiao Ding; Shun-Lin Li (Natural Product Research, 2022)

The genes for sensory perception of sound should be considered in gene diagnosis of congenital sensorineural hearing loss and microtia - Ken Lin; Ding-Yun You; Li-Huan Zhang; Li-Juan Zhou; Jin-Yan Zu; Yang Xiao; Mei-Hua Sun; Dong-Su; Xue Cao; Tie-Song Zhang; Jing Ma (Journal of Applied Genetics, 2022)

Two new 7,20-epoxy- ent -kaurane diterpenoids from the aerial parts of Isodon serra - Juan-Juan Hu; Bai-Lin Li; Jin-Dan Xie; Hui-Jun Liang; Qian-Ran Li; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2022)

Crocin Alleviates Intracerebral Hemorrhage–Induced Neuronal Ferroptosis by Facilitating Nrf2 Nuclear Translocation - Fei Wang; Wu-lin Li; Li-juan Shen; Ting-ting Jiang; Jian-jun Xia; Da-li You; Shan-you Hu; Li Wang; Xiao Wu (Neurotoxicity Research, 2022)

Follicular Fluid-Derived Exosomal MicroRNA-18b-5p Regulates PTEN-Mediated PI3K/Akt/mTOR Signaling Pathway to Inhibit Polycystic Ovary Syndrome Development - Zhi Zhou; Zhihua Tu; Juan Zhang; Can tan; Xiaoyong Shen; Bangbei Wan; Yejuan Li; Anguo Wang; Liqiang Zhao; Jiajia Hu; Ning Ma; Jing Zhou; et al. (Molecular Neurobiology, 2022)

Pollution characteristics and emissions of typical organophosphate esters of a wastewater treatment plant - Hongling Yin; Yi Luo; Jiaojiao Song; Shiping Li; Shuyu Lin; Yuanming Xiong; Shuhong Fang; Juan Tang (Environmental Science and Pollution Research, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Air pollution increased risk of reproductive system diseases: a 5-year outcome analysis of different pollutants in different seasons, ages, and genders - Ya Li; Juan Du; Shanshan Lin; Huihui He; Rui Jia; Weihong Liu (Environmental Science and Pollution Research, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Evolutionary characteristics and phylogeny of cotton chloroplast tRNAs - Ning Wang; Wan-Lin Dong; Xiao-Jing Zhang; Tong Zhou; Xiao-Juan Huang; Bao-Guo Li; Jian-Ni Liu; Xiong-Feng Ma; Zhong-Hu Li (Planta, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Three new ester glycosides with cytotoxic activity from the seeds of Caesalpinia sappan - Min Wang; Juan Tan; Jun Chen; Tian Xie; Liang-Mo Lin; Li-Li Zhong; Xing-Jun Cai; Qiong-Shi Wu (Natural Product Research, 2021)

Untargeted metabolomic analysis of urine samples for diagnosis of inherited metabolic disorders - Hao Liu; Jiang Zhu; Qiu Li; Dongjuan Wang; Kexing Wan; Zhaojian Yuan; Juan Zhang; Lin Zou; Xiaoyan He; Jingkun Miao (Functional & Integrative Genomics, 2021)

Interaction between the cell walls of microalgal host and fungal carbohydrate‐activate enzymes is essential for the pathogenic parasitism process - Juan Lin; Hailong Yan; Liang Zhao; Yanhua Li; Bahareh Nahidian; Mianmian Zhu; Qiang Hu; Danxiang Han (Environmental Microbiology, 2021)
Summary Fungi can parasitize microalgae, exerting profound impacts on both the aquatic ecosystems and microalgal mass cultures. In this study, the unicellular green alga Haematococcus pluvialis and the blastocladialean fungus Paraphysoderma sedebokerense were used as a model system to address the mechanisms underlying the fungal parasitism on the algal host. High‐throughput metabolic assay indicated that P . sedebokerense can utilize several carbon sources with a preference for mannose, glucose and their oligosaccharides, which was compatible with the profile of the host algal cell walls enriched with glucan and mannan. The results of dual transcriptomics analysis suggested that P . sedebokerense can upregulate a large number of putative carbohydrate‐activate enzymes (CAZymes) encoding genes, including those coding for the endo‐1,4‐β‐glucanase and endo‐1,4‐β‐mannanase during the infection process. The cell walls of H . pluvialis can be decomposed by both P . sedebokerense and commercial CAZymes (e.g. cellulase and endo‐1,4‐β‐mannanase) to produce mannooligomers, while several putative parasitism‐related genes of P . sedebokerense can be in turn upregulated by mannooligomers. In addition, the parasitism can be blocked by interfering the selected CAZymes including glucanase, mannanase and lysozyme with the specific inhibitors, which provided a framework for screening suitable compounds for pathogen mitigation in algal mass culture.

Proteomics provides individualized options of precision medicine for patients with gastric cancer - Wenwen Huang; Dongdong Zhan; Yazhuo Li; Nairen Zheng; Xin Wei; Bin Bai; Kecheng Zhang; Mingwei Liu; Xuefei Zhao; Xiaotian Ni; Xia Xia; Jinwen Shi; et al. (Science China Life Sciences, 2021)

Different posterior hippocampus and default mode network modulation in young APOE ε4 carriers: a functional connectome-informed phenotype longitudinal study - Li Juan Zheng; Li Lin; U. Joseph Schoepf; Akos Varga-Szemes; Rock H. Savage; Han Zhang; Yun Fei Wang; Xin Yuan Zhang; Song Luo; Ya Liu; Gui Fen Yang; Guang Ming Lu; et al. (Molecular Neurobiology, 2021)

Ghrelin Affects Gastric Cancer Progression by Activating AMPK Signaling Pathway - Xiao-Lin Hu; Yong-Jun Zhu; Chang-Hua Hu; Li You; Juan Wu; Xiao-Yan He; Wen-Jie Huang; Zong-Hui Wu (Biochemical Genetics, 2021)

Rosanortriterpenes A–B, two new nortriterpenes from the fruits of Rosa laevigata var. leiocapus - Yu-Nong Tian; Bai-Lin Li; Juan-Juan Hu; Jin-Dan Xie; Wen-Jing Xiao; Ling-Hui Nie; Jie-Wei Wu (Natural Product Research, 2021)

TLR8 in the Trigeminal Ganglion Contributes to the Maintenance of Trigeminal Neuropathic Pain in Mice - Lin-Xia Zhao; Ming Jiang; Xue-Qiang Bai; De-Li Cao; Xiao-Bo Wu; Jing Zhang; Jian-Shuang Guo; Tong-Tong Chen; Juan Wang; Hao Wu; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)
Trigeminal neuropathic pain (TNP) is a significant health problem but the involved mechanism has not been completely elucidated. Toll-like receptors (TLRs) have recently been demonstrated to be expressed in the dorsal root ganglion and involved in chronic pain. Here, we show that TLR8 was persistently increased in the trigeminal ganglion (TG) neurons in model of TNP induced by partial infraorbital nerve ligation (pIONL). In addition, deletion or knockdown of Tlr8 in the TG attenuated pIONL-induced mechanical allodynia, reduced the activation of ERK and p38-MAPK, and decreased the expression of pro-inflammatory cytokines in the TG. Furthermore, intra-TG injection of the TLR8 agonist VTX-2337 induced pain hypersensitivity. VTX-2337 also increased the intracellular Ca 2+ concentration, induced the activation of ERK and p38, and increased the expression of pro-inflammatory cytokines in the TG. These data indicate that TLR8 contributes to the maintenance of TNP through increasing MAPK-mediated neuroinflammation. Targeting TLR8 signaling may be effective for the treatment of TNP.

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Evaluating the effect of midpalatal corticotomy-assisted rapid maxillary expansion on the upper airway in young adults using computational fluid dynamics - Juan Li; Lingfang Shi; Xiayao Zhang; Luxi Weng; Hong Chen; Jun Lin (Journal of Zhejiang University-SCIENCE B, 2021)

First report of turnip mosaic virus on yellow passion fruit in China - Li Juan Chen; Xing Xing Zhang; Ying Lin Lu; Yu Xing An (Journal of Plant Pathology, 2021)

Using sowing date management to promote micronutrient quality and alleviate cadmium accumulation in rice grains - Lin-lin Shi; Ming-xing Shen; Hong-jun Wu; Chang-ying Lu; Li-juan Mei; Xin-lian Zhu; Hai-hou Wang; Yun-Sheng Song (Cereal Research Communications, 2020)

Gut dysbiosis-influence on amygdala-based functional activity in patients with end stage renal disease: a preliminary study - Li Juan Zheng; Li Lin; Jianhui Zhong; Zhihong Zhang; Yu Bing Ye; Xin Yuan Zhang; Yun Fei Wang; Han Zhang; Ya Liu; Guang Ming Lu; Dehua Gong; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

First report of ramie mosaic virus on passion fruit in Guangdong, southern China - Li Juan Chen; Dong Lei Sun; Ying Lin Lu; Yu Xing An (Journal of Plant Pathology, 2020)

Assimilation of exogenous cyanide cross talk in Oryza sativa L. to the key nodes in nitrogen metabolism - Cheng-Zhi Li; Li Yang; Yu-Juan Lin; Hua Zhang; Saeed Rad; Xiao-Zhang Yu (Ecotoxicology, 2020)

Surface display system for probiotics and its application in aquaculture - Yuan‐Yuan Yao; Ya‐Lin Yang; Chen‐Chen Gao; Feng‐Li Zhang; Rui Xia; Dong Li; Juan Hu; Chao Ran; Zhen Zhang; Jihong Liu‐Clarke; Zhi‐Gang Zhou (Reviews in Aquaculture, 2020)
Aquaculture is a fast‐growing and rapidly expanding industry in the world. Probiotics are widely used in aquaculture and have provided benefits to aquatic animal health, and it is also a promising alternative to antibiotics for control of fish diseases. With the development of biotechnology, new expression systems and novel techniques for the surface display of heterologous proteins in surface of probiotics cells have been developed. This review provides an overview of the systems and strategies for displaying functional proteins on the surface of probiotics commonly used in aquaculture, which are Bacillus subtilis , Bacillus thuringiensis , lactic acid bacteria represented by Lactococcus lactis and yeast. Their applications in aquaculture especially for oral vaccine development afforded by this technology and prospects and challenges associated with this technology are also highlighted.

Identification of Cyt2Ba from a New Strain of Bacillus thuringiensis and Its Toxicity in Bradysia difformis - Fan-Fan Wang; Shao-Xuan Qu; Jin-Sheng Lin; Hui-Ping Li; Li-Juan Hou; Ning Jiang; Xin Luo; Lin Ma (Current Microbiology, 2020)
Bradysia difformis is one of the most damaging pests in mushroom production in China. In this study, eight Bacillus thuringiensis strains were analyzed for insecticidal activity in B. difformis . The strain JW-1 showed the highest insecticidal activity against B. difformis larvae, but did not inhibit the mycelial growth of Pleurotus ostreatus and P. geesteranus . The 16S rRNA gene (1397 bp) and cyt2 gene (792 bp) were obtained from strain JW-1. The phylogenetic tree based on 16S rRNA gene and Cyt2 toxin showed that strain JW-1 was a member of B. thuringiensis and Cyt2 toxin belonged to Cyt2Ba toxin cluster. The Cyt2Ba toxin from strain JW-1 was overexpressed in E. coli as a fusion protein and the fusion protein (70 kDa) was purified by Ni-IDA affinity chromatography. The purified Cyt2Ba fusion protein was toxic to B. difformis larvae (LC 50 was 2.25 ng/mL). The identification of Cyt2Ba from strain JW-1 and confirmation of the insecticidal activity of Cyt2Ba in B. difformis provided a new means of biological control of the important pest in mushroom production.

Sodium Para-aminosalicylic Acid Reverses Changes of Glutamate Turnover in Manganese-Exposed Rats - Zhao-Cong Li; Fang Wang; Shao-Jun Li; Lin Zhao; Jun-Yan Li; Yue Deng; Xiao-Juan Zhu; Yu-Wen Zhang; Dong-Jie Peng; Yue-Ming Jiang (Biological Trace Element Research, 2020)

Small RNA profiling reveal regulation of microRNAs in field peanut pod rot pathogen infection - Mian Wang; Chao-xin Zhang; Li-juan Pan; Tong Wang; Na Chen; Ming-na Chen; Zhen Yang; Xin-gang Guo; Shan-lin Yu; Xiao-yuan Chi (Biologia, 2020)

Short-term associations between ambient fine particulate matter pollution and hospital visits for chronic obstructive pulmonary disease in Yinzhou District, China - Cheng-yi Lin; Die Li; Jie-ming Lu; Zhe-bin Yu; Yao Zhu; Peng Shen; Meng-ling Tang; Ming-juan Jin; Hong-bo Lin; Li-ming Shui; Kun Chen; Jian-bing Wang (Environmental Science and Pollution Research, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Identification of novel functional CpG-SNPs associated with type 2 diabetes and coronary artery disease - Zun Wang; Chuan Qiu; Xu Lin; Lan-Juan Zhao; Yong Liu; Xinrui Wu; Qian Wang; Wei Liu; Kelvin Li; Hong-Wen Deng; Si-Yuan Tang; Hui Shen (Molecular Genetics and Genomics, 2020)

First report of Fusarium oxysporum f. sp. canariensis causing Fusarium wilt on Canary Island date palm (Phoenix canariensis Hort. Ex Chabaud) in China - Cheng Zhong Lan; Yu Li Dai; Lin Gan; Jin Ai Yao; Xiu Juan Yang (Journal of Plant Pathology, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Abnormal differentiation of regulatory T cells and Th17 cells induced by perinatal bisphenol A exposure in female offspring mice - You-dan Dong; Liang Gao; Feng-juan Wu; Ren Lin; Yuan Meng; Li-hong Jia; Xiao-fei Wang (Molecular & Cellular Toxicology, 2020)

Viral metagenomics reveals sapoviruses of different genogroups in stool samples from children with acute gastroenteritis in Jiangsu, China - Wang Li; Surong Dong; Juan Xu; Xiaobin Zhou; Junling Han; Zhaqing Xie; Qin Gong; Hailin Peng; Chenglin Zhou; Mei Lin (Archives of Virology, 2020)
Sapoviruses (SAVs), including several genogroups (GI to GV), are one of the causes of acute gastroenteritis (AGE). In this study, viral metagenomics revealed the presence of sapoviruses of different genogroups in stool from children with AGE. Eight different complete SAV genomes were determined, of which five belonged to GI and the other three belonged to GII, GIV and GV, respectively. Although they were highly similar to published sequences, the GIV and GV were the first complete genome sequences of these SAVs found in China. In a prevalence investigation, 19% of subjects with AGE were positive for SAVs, while none of the control group was positive.

Novel mutations in SPEF2 causing different defects between flagella and cilia bridge: the phenotypic link between MMAF and PCD - Chaofeng Tu; Hongchuan Nie; Lanlan Meng; Weili Wang; Haiyu Li; Shimin Yuan; Dehua Cheng; Wenbin He; Gang Liu; Juan Du; Fei Gong; Guangxiu Lu; et al. (Human Genetics, 2020)

Multicenter-Based Population Pharmacokinetic Analysis of Ciclosporin in Hematopoietic Stem Cell Transplantation Patients - Ling Xue; Wen-juan Zhang; Ji-xin Tian; Lin-na Liu; Hai-hong Yan; Wen-wen Zhang; Xiao-liang Ding; Jing-jing Zhang; Li-yan Miao (Pharmaceutical Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Cloning and Expression Analysis of the ScD53 Gene from Sugarcane - Ai-Li Lv; Xu-Juan Li; Chun-Jia Li; Hong-Bo Liu; Qiu-Yan Zi; Xiu-Qin Lin; Xin-Long Liu (Sugar Tech, 2019)

Stabilization of hydrophobic organic contaminants in sediments by natural zeolites: bioavailability-based assessment of efficacy using equilibrium passive sampling - Yiqin Chen; Wenjian Yu; Ling Jin; Qian Wang; Jie Yin; Jianwei Lin; Juan-Ying Li (Journal of Soils and Sediments, 2019)

Cloning and expression analysis of the StCUL1 gene in potato - Peng-Xiang Pang; Li Shi; Xiao-Juan Wang; Yan-Nan Chang; Yong-Ping Luo; Jin-Lin Feng; Hemu Eri; Gang Gao (Journal of Plant Biochemistry and Biotechnology, 2019)

Climate warming alters subsoil but not topsoil carbon dynamics in alpine grassland - Juan Jia; Zhenjiao Cao; Chengzhu Liu; Zhenhua Zhang; Li Lin; Yiyun Wang; Negar Haghipour; Lukas Wacker; Hongyan Bao; Thorston Dittmar; Myrna J. Simpson; Huan Yang; et al. (Global Change Biology, 2019)
Subsoil contains more than half of soil organic carbon (SOC) globally and is conventionally assumed to be relatively unresponsive to warming compared to the topsoil. Here, we show substantial changes in carbon allocation and dynamics of the subsoil but not topsoil in the Qinghai‐Tibetan alpine grasslands over 5 years of warming. Specifically, warming enhanced the accumulation of newly synthesized ( 14 C‐enriched) carbon in the subsoil slow‐cycling pool (silt‐clay fraction) but promoted the decomposition of plant‐derived lignin in the fast‐cycling pool (macroaggregates). These changes mirrored an accumulation of lipids and sugars at the expense of lignin in the warmed bulk subsoil, likely associated with shortened soil freezing period and a deepening root system. As warming is accompanied by deepening roots in a wide range of ecosystems, root‐driven accrual of slow‐cycling pool may represent an important and overlooked mechanism for a potential long‐term carbon sink at depth. Moreover, given the contrasting sensitivity of SOC dynamics at varied depths, warming studies focusing only on surface soils may vastly misrepresent shifts in ecosystem carbon storage under climate change.

Quantifying Flood Frequency Modification Caused by Multi-Reservoir Regulation - Yi-han Tang; Jie-feng Wu; Pei-yi Li; Li-juan Zhang; Xiao-hong Chen; Kai-rong Lin (Water Resources Management, 2019)

Reducing ammonia and greenhouse gas emission with adding high levels of superphosphate fertilizer during composting - Juan Wu; Shengzhou He; Guoxue Li; Zehua Zhao; Yuquan Wei; Zhong Lin; De Tao (Environmental Science and Pollution Research, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Involvement of glutamate receptors in regulating calcium influx in rice seedlings under Cr exposure - Yan-Hong Li; Xiao-Zhang Yu; Ling-Yun Mo; Yu-Juan Lin; Qing Zhang (Ecotoxicology, 2019)

Expression patterns of alpha-amylase and beta-amylase genes provide insights into the molecular mechanisms underlying the responses of tea plants (Camellia sinensis) to stress and postharvest processing treatments - Chuan Yue; Hongli Cao; Hongzheng Lin; Juan Hu; Yijun Ye; Jiamin Li; Zhilong Hao; Xinyuan Hao; Yun Sun; Yajun Yang; Xinchao Wang (Planta, 2019)

Heavy metals and PAHs in an open fishing area of the East China Sea: Multimedia distribution, source diagnosis, and dietary risk assessment - Qian Wang; Fei Peng; Yiqin Chen; Ling Jin; Jun Lin; Xu Zhao; Jie Yin; Juan-Ying Li (Environmental Science and Pollution Research, 2019)

Regulatory Roles of Peroxisomal Metabolic Pathways Involved in Musk Secretion in Muskrats - Meishan Zhang; Shuang Yang; Minghui Shi; Shumiao Zhang; Tianxiang Zhang; Yimeng Li; Shanghua Xu; Muha Cha; Yuping Meng; Shaobi Lin; Juan Yu; Xuxin Li; et al. (The Journal of Membrane Biology, 2019)

Neuroinflammation, Gut Microbiome, and Alzheimer’s Disease - Li Lin; Li Juan Zheng; Long Jiang Zhang (Molecular Neurobiology, 2018)

Acute effect of fine and coarse particular matter on cardiovascular visits in Ningbo, China - Pei-wen Zheng; Peng Shen; Zhen-hua Ye; Zhen-yu Zhang; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Jian-bing Wang; Kun Chen (Environmental Science and Pollution Research, 2018)

Lack of Association Between DNMT3B Polymorphisms and Sporadic Parkinson’s Disease in a Han Chinese Population - Hong Pan; Jun-Yi Shen; Juan-Juan Du; Shi-Shuang Cui; Jin Liu; Yi-Qi Lin; Yi-Xi He; Yang Fu; Chao Gao; Gen Li; Sheng-Di Chen; Jian-Fang Ma (Neuroscience Bulletin, 2018)

Extreme Sea Level Rise off the Northwest Coast of the South China Sea in 2012 - Lin Liu; Juan Li; Wei Tan; Yue Wu; Yanliang Liu; Huiwu Wang (Journal of Ocean University of China, 2018)

Exploration of phenol tolerance mechanism through antioxidative responses of an evolved strain, Chlorella sp. L5 - Lin Zhou; Yizhong Yuan; Xuyang Li; Shouhua Mei; Juan Gao; Quanyu Zhao; Wei Wei; Yuhan Sun (Journal of Applied Phycology, 2018)

mRNA Analysis of Genes Encoded with Phytochelatin Synthase (PCS) in Rice Seedlings Exposed to Chromium: The Role of Phytochelatins in Cr Detoxification - Xiao-Zhang Yu; Qin-Long Ling; Yan-Hong Li; Yu-Juan Lin (Bulletin of Environmental Contamination and Toxicology, 2018)

Association between short-term exposure to ambient air pollution and daily mortality: a time-series study in Eastern China - Die Li; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Pei-wen Zheng; Ming-juan Jin; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2018)

A new pair of enantiomeric lignans from the fruits of Morinda citrifolia and their absolute configuration - Wen-Jian Liu; Yue-Juan Chen; Dan-Na Chen; Ya-Ping Wu; Yu-Jie Gao; Jing Li; Wen-Jun Zhong; Lin Jiang (Natural Product Research, 2018)

Interferon activates promoter of Nmi gene via interferon regulator factor-1 - Xiao Xu; Keli Chai; Yuhang Chen; Yongquan Lin; Suzhen Zhang; Xin Li; Wentao Qiao; Juan Tan (Molecular and Cellular Biochemistry, 2018)

Species-based classification reveals spatial processes of phytoplankton meta-communities better than functional group approaches: a case study from three freshwater lake regions in China - Li-Juan Xiao; Yiqiu Zhu; Yang Yang; Qiuqi Lin; Bo-Ping Han; Judit Padisák (Hydrobiologia, 2018)

Effects of air pollution on hospital visits for pneumonia in children: a two-year analysis from China - Die Li; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Pei-wen Zheng; Ming-juan Jin; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2018)

Tobacco alpha-expansin EXPA4 plays a role in Nicotiana benthamiana defence against Tobacco mosaic virus - Li-Juan Chen; Wen-Shan Zou; Guo Wu; Hong-Hui Lin; De-Hui Xi (Planta, 2018)

Effect of the dark septate endophytic fungus Acrocalymma vagum on heavy metal content in tobacco leaves - Hui-Qing Jin; Hua-Bing Liu; Ying-Ying Xie; Yong-Gang Zhang; Qing-Quan Xu; Li-Juan Mao; Xin-Jun Li; Jin Chen; Fu-Cheng Lin; Chu-Long Zhang (Symbiosis, 2018)

Erratum to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Construction of Dual Pore 3-D Digital Cores with a Hybrid Method Combined with Physical Experiment Method and Numerical Reconstruction Method - Wei Lin; Xizhe Li; Zhengming Yang; Juan Wang; Shengchun Xiong; Yutian Luo; Guoming Wu (Transport in Porous Media, 2017)

Air pollution and hospital visits for acute upper and lower respiratory infections among children in Ningbo, China: A time-series analysis - Pei-wen Zheng; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2017)

Decolorization of textile dye RB19 using volcanic rock matrix immobilized Bacillus thuringiensis cells with surface displayed laccase - Juan Wan; Xiaowen Sun; Cheng Liu; Mengjun Tang; Lin Li; Hong Ni (World Journal of Microbiology and Biotechnology, 2017)

Intelligent diagnosis of jaundice with dynamic uncertain causality graph model - Shao-rui Hao; Shi-chao Geng; Lin-xiao Fan; Jia-jia Chen; Qin Zhang; Lan-juan Li (Journal of Zhejiang University-SCIENCE B, 2017)

Transplantation of collagen scaffold with autologous bone marrow mononuclear cells promotes functional endometrium reconstruction via downregulating ΔNp63 expression in Asherman’s syndrome - Guangfeng Zhao; Yun Cao; Xianghong Zhu; Xiaoqiu Tang; Lijun Ding; Haixiang Sun; Juan Li; Xinan Li; Chenyan Dai; Tong Ru; Hui Zhu; Jingjie Lu; et al. (Science China Life Sciences, 2017)

Developmental changes in digestive enzyme activity in American shad, Alosa sapidissima, during early ontogeny - Xiao-Qiang Gao; Zhi-Feng Liu; Chang-Tao Guan; Bin Huang; Ji-Lin Lei; Juan Li; Zheng-Long Guo; Yao-Hui Wang; Lei Hong (Fish Physiology and Biochemistry, 2017)

Effects of soybean meal processing treatments on growth performance, nutrient digestibility, nitrogen and phosphorus excretion in red swamp crayfish, Procambarus clarkii - Jin-juan Wan; Mei-fang Shen; Jian-qing Tang; Hai Lin; Wei-hui Yan; Jia-jia Li; Lin Zhu (Aquaculture International, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Celastrol, produced by Tripterygium wilfordii Hook F. enhances defense response in cucumber seedlings against diverse environmental stresses - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Peng-xu Li; Jun-qiang Wu; Da-wei Zhang; Honghui Lin (Journal of Plant Biology, 2017)

Prolonged exposure to low-dose microcystin induces nonalcoholic steatohepatitis in mice: a systems toxicology study - Jun He; Guangyu Li; Jun Chen; Juan Lin; Cheng Zeng; Jing Chen; Junliang Deng; Ping Xie (Archives of Toxicology, 2017)

Improved salt tolerance of medicinal plant Codonopsis pilosula by Bacillus amyloliquefaciens GB03 - Qing-Qing Han; Yong-Na Wu; Hui-Juan Gao; Rui Xu; Paul W. Paré; Huazhong Shi; Qi Zhao; Hui-Ru Li; Sardar Ali Khan; Yin-Quan Wang; Suo-Min Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2017)

In vitro remineralization of hybrid layers using biomimetic analogs - Hui-ping Lin; Jun Lin; Juan Li; Jing-hong Xu; Christian Mehl (Journal of Zhejiang University-SCIENCE B, 2016)

Aneuploid progenies of triploid hybrids between diploid and tetraploid loach Misgurnus anguillicaudatus in China - Ya-Juan Li; Yang-Chun Gao; He Zhou; Hai-Yan Ma; Zhong-Qiao Lin; Tian-Yu Ma; Yi Sui; Katsutoshi Arai (Genetica, 2016)

Erratum to: Progressive changes of orexin system in a rat model of 6-hydroxydopamine-induced Parkinson’s disease - Long-Biao Cui; Bo-Wei Li; Xiao-Hang Jin; Lin Zhao; Juan Shi (Neuroscience Bulletin, 2016)

Reverse transcription genome exponential amplification reaction assay for rapid and universal detection of human rhinoviruses - Li Guan; Lin-Qing Zhao; Hang-Yu Zhou; Kai Nie; Xin-Na Li; Dan Zhang; Juan Song; Yuan Qian; Xue-Jun Ma (Archives of Virology, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Effects of seasonal variations on soil microbial community composition of two typical zonal vegetation types in the Wuyi Mountains - Ze-yan Wu; Wen-xiong Lin; Jian-juan Li; Jin-fu Liu; Bai-lian Li; Lin-kun Wu; Chang-xun Fang; Zhi-xing Zhang (Journal of Mountain Science, 2016)

Spatio-temporal distribution of flood disasters and analysis of influencing factors in Africa - Chan-juan Li; Yuan-qing Chai; Lin-sheng Yang; Hai-rong Li (Natural Hazards, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Proanthocyanidins accelerate the germination of cucumber (Cucumis sativus L.) seeds - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Jun-qiang Wu; Da-wei Zhang; Hong-hui Lin (Journal of Plant Biology, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Efficacy of dexmedetomidine with cognitive behavioral therapy for treating chronic insomnia related to conditioned arousal: a randomized controlled trial - Xunjun Li; Xiaojiang Jiang; Yazhen Liu; Ying Lang; Yuanyuan Ye; Ling Lin; Juan Liu; Yuanfeng Zhang (Sleep and Biological Rhythms, 2016)

Enteractinococcus lamae sp. nov. and Enteractinococcus viverrae sp. nov., isolated from animal faeces - Xiu Chen; Gui-Ding Li; Qin-Yuan Li; Cai-Juan Hu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang; Li Han; Xue-Shi Huang (Antonie van Leeuwenhoek, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Effects of light intensity on the susceptibility of Nicotiana tabacum to cucumber mosaic virus - Li-Juan Chen; Han Ren; Xing-Guang Deng; Ya-Nan Li; Wen-Qiong Cha; Hong-Hui Lin; De-Hui Xi (Journal of General Plant Pathology, 2015)

Characterisation of the dark green islands of cucumber mosaic virus infected Nicotiana tabacum - Li-Juan Chen; Jian Liu; Fei-Fei Zhao; Jing-Yi Li; Sheng-Xuan Wang; Hong-Hui Lin; De-Hui Xi (Plant Cell Reports, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Activation of Dopamine D1 Receptors Regulates Dendritic Morphogenesis Through Rac1 and RhoA in Prefrontal Cortex Neurons - Juan Li; Jingjing Gu; Bin Wang; Minjuan Xie; Lu Huang; Yutong Liu; Lei Zhang; Jinhua Xue; Fukun Guo; Lin Zhang; Lu Zhang (Molecular Neurobiology, 2015)

ERK Is Involved in the Process of Acrosome Reaction In Vitro of the Chinese Mitten Crab, Eriocheir sinensis - Wen-Juan Sun; Ming Zhu; Yuan-Li Wang; Qing Li; Hong-Dan Yang; Ze-Lin Duan; Lin He; Qun Wang (Marine Biotechnology, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

Morphological alterations of all stages of spermatogenesis and acrosome reaction in Chinese mitten crab Eriocheir sinensis - Yuan-Li Wang; Wen-Juan Sun; Lin He; Qing Li; Qun Wang (Cell and Tissue Research, 2015)

Ectopic expression of a phytochrome B gene from Chinese cabbage (Brassica rapa L. ssp. pekinensis) in Arabidopsis thaliana promotes seedling de-etiolation, dwarfing in mature plants, and delayed flowering - Mei-Fang Song; Shu Zhang; Pei Hou; Hong-Zhong Shang; Hai-Ke Gu; Jing-Juan Li; Yang Xiao; Lin Guo; Liang Su; Jian-Wei Gao; Jian-Ping Yang (Plant Molecular Biology, 2015)

Studies on mitogen-activated protein kinase signaling pathway in the alveolar macrophages of chronic bronchitis rats - Yan Huang; Xiao-Ming Meng; Guo-Lin Jiang; Ya-Ru Yang; Juan Liu; Xiong-Wen Lv; Jun Li (Molecular and Cellular Biochemistry, 2015)

Association of IL-18 promoter gene polymorphisms with rheumatoid arthritis: a meta-analysis - Li-Ping Cai; Li-Juan Zhou; Shun-Yu Lu; Ying-E Liang; Xiao-Ying Chen; Lin Liu; Jun Lin (Molecular Biology Reports, 2014)

The Association Between Single Nucleotide Polymorphisms of GSK 3β Gene and Sporadic Alzheimer’s Disease in a Cohort of Southern Chinese Han Population - Jing Li; Fan Zeng; Juan Deng; Jie Zhu; Lin Li; Tao Zhang; Juan Liu; Li–Li Zhang; Chang-Yue Gao; Meng Zhang; Zhi-Qiang Xu; Hua-Dong Zhou; et al. (Neurotoxicity Research, 2014)

TM4SF1: a new vascular therapeutic target in cancer - Chi-Iou Lin; Anne Merley; Tracey E. Sciuto; Dan Li; Ann M. Dvorak; Juan M. Melero-Martin; Harold F. Dvorak; Shou-Ching S. Jaminet (Angiogenesis, 2014)

A more sensitive and rapid multiplex RT-PCR assay combining with magnetic nanobeads for simultaneous detection of viruses in sweet potato - Xing-Guang Deng; Feng Zhu; Ying-Juan Chen; Jian Liu; Tong Zhu; Jing-Yi Li; De-Hui Xi; Hong-Hui Lin (European Journal of Plant Pathology, 2014)

Down-regulation of Gli-1 inhibits hepatocellular carcinoma cell migration and invasion - Jing-Song Chen; Hua-Shu Li; Jiong-Qiang Huang; Long-Juan Zhang; Xi-Lin Chen; Qian Wang; Jian Lei; Ju-Tao Feng; Qin Liu; Xiao-Hui Huang (Molecular and Cellular Biochemistry, 2014)

Protective effect of indomethacin in renal ischemia-reperfusion injury in mice - Sheng-hong Zhu; Li-jia Zhou; Hong Jiang; Rong-jun Chen; Chuan Lin; Shi Feng; Juan Jin; Jiang-hua Chen; Jian-yong Wu (Journal of Zhejiang University-SCIENCE B, 2014)

Gordonia jinhuaensis sp. nov., a novel actinobacterium, isolated from a VBNC (viable but non-culturable) state in pharmaceutical wastewater - Shan-Hui Li; Yi Jin; Juan Cheng; Dong-Jin Park; Chang-Jin Kim; Wael N. Hozzein; Mohammed A. M. Wadaan; Wen-Sheng Shu; Lin-Xian Ding; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Urinary Perchlorate Exposure and Risk in Women of Reproductive Age in a Fireworks Production Area of China - Qin Li; Yun-jiang Yu; Fei-fei Wang; Shi-wu Chen; Yan Yin; Hai-peng Lin; Fei Che; Peng Sun; Juan Qin; Jie Liu; Hong-mei Wang (Archives of Environmental Contamination and Toxicology, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

hABCF3, a TPD52L2 interacting partner, enhances the proliferation of human liver cancer cell lines in vitro - Juan Zhou; Ying Lin; Huili Shi; Keke Huo; Yanhong Li (Molecular Biology Reports, 2013)

Human white adipose tissue vasculature contains endothelial colony-forming cells with robust in vivo vasculogenic potential - Ruei-Zeng Lin; Rafael Moreno-Luna; Rocio Muñoz-Hernandez; Dan Li; Shou-Ching S. Jaminet; Arin K. Greene; Juan M. Melero-Martin (Angiogenesis, 2013)

Requests for Health Education from Chinese Cancer Patients During Their Recovery Period: a Cross-Sectional Study - Wei-Li Qiu; Pei-Juan Lin; Fei-Qun Ruan; Xiao Wu; Miao-Ping Lin; Lian Liu; Jia-Yi Luo; Kun Lin (Journal of Cancer Education, 2013)

Different Gene Expressions of Resistant and Susceptible Maize Inbreds in Response to Fusarium verticillioides Infection - Guangsheng Yuan; Zhiming Zhang; Kui Xiang; Yaou Shen; Juan Du; Haijian Lin; Li Liu; Maojun Zhao; Guangtang Pan (Plant Molecular Biology Reporter, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Analysis of artificial corner reflector’s radar cross section: a physical optics perspective - Xin-Jian Shan; Jing-Yuan Yin; Dan-Lin Yu; Cheng-Fan Li; Jun-Juan Zhao; Gui-Fang Zhang (Arabian Journal of Geosciences, 2013)

Converting paddy fields to Lei bamboo (Phyllostachys praecox) stands affected soil nutrient concentrations, labile organic carbon pools, and organic carbon chemical compositions - Tao Zhang; Yongfu Li; Scott X. Chang; Peikun Jiang; Guomo Zhou; Juan Liu; Lin Lin (Plant and Soil, 2013)

Construction and analysis of different expression cDNA libraries in Rehmannia glutinosa plants subjected to continuous cropping - Yan Hui Yang; Zhong Yi Zhang; Hua Min Fan; Yi Dan Zhao; Ming Jie Li; Juan Li; Jun Ying Chen; Wen Xiong Lin; Xin Jian Chen (Acta Physiologiae Plantarum, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Interactions of interleukin-12A and interleukin-12B polymorphisms on the risk of intracranial aneurysm - Li-Juan Li; Xin-Min Pan; Xiutian Sima; Zhao-Hui Li; Lu-Shun Zhang; Hong Sun; Yi Zhu; Wei-Bo Liang; Lin-Bo Gao; Lin Zhang (Molecular Biology Reports, 2012)

NADPH oxidase 2 plays a critical role in dysfunction and apoptosis of pancreatic β-cells induced by very low-density lipoprotein - Juan Jiao; Lin Dou; Miao Li; Yonggang Lu; Han-Bang Guo; Yong Man; Shu Wang; Jian Li (Molecular and Cellular Biochemistry, 2012)

Protective effects of Lycium barbarum polysaccharide on neonatal rat primary cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion - Chen Rui; Li Yuxiang; Hao Yinju; Zhu Qingluan; Wu Yang; Zhao Qipeng; Wang Hao; Ma Lin; Liu Juan; Zhao Chengjun; Jiang Yuanxu; Wang Yanrong; et al. (Journal of Molecular Histology, 2012)

Identification, fine mapping and characterization of Rht-dp, a recessive wheat dwarfing (reduced height) gene derived from Triticum polonicum - Hou-Yang Kang; Li-Juan Lin; Zhi-Jian Song; Jing-Ya Yuan; Mei-Yu Zhong; Hai-Qin Zhang; Xing Fan; Li-Na Sha; Yi Wang; Li-Li Xu; Jian Zeng; Yong-Hong Zhou (Genes & Genomics, 2012)

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

Calreticulin Mediates Nerve Growth Factor-Induced Neuronal Differentiation - Yu-Yin Shih; Akira Nakagawara; Hsinyu Lee; Hsueh-Fen Juan; Yung-Ming Jeng; Dong-Tsamn Lin; Yung-Li Yang; Yeou-Guang Tsay; Min-Chuan Huang; Chien-Yuan Pan; Wen-Ming Hsu; Yung-Feng Liao (Journal of Molecular Neuroscience, 2012)

Effects of sucrose concentration and exogenous hormones on growth and periplocin accumulation in adventitious roots of Periploca sepium Bunge - Jian Zhang; Wen-Yuan Gao; Juan Wang; Xing-lin Li (Acta Physiologiae Plantarum, 2012)

Prevention and treatment of allergic inflammation by an Fcγ-Der f2 fusion protein in a murine model of dust mite-induced asthma - Li-hui Lin; Ping Zheng; John W. M. Yuen; Juan Wang; Juan Zhou; Cun-quan Kong; Xia Peng; Jia Li; Li Li (Immunologic Research, 2012)

Synthesis and Bioactive Studies of Complex 8-Hydroxyquinolinato-Bis-(Salicylato) Yttrium (III) - Xu Li; Qiang-Guo Li; Hui Zhang; Ji-Lin Hu; Fei-Hong Yao; De-Jun Yang; Sheng-Xiong Xiao; Li-Juan Ye; Yi Huang; Dong-Cai Guo (Biological Trace Element Research, 2012)

Molecular characterization of β-lactam-resistant Escherichia coli isolated from Fu River, China - Li-Kou Zou; Li-Wen Li; Xin Pan; Guo-Bao Tian; Yan Luo; Qi Wu; Bei Li; Lin Cheng; Jiu-Jing Xiao; Su Hu; Yang Zhou; Yu-Juan Pang (World Journal of Microbiology and Biotechnology, 2012)

SIRT1 is required for long-term growth of human mesenchymal stem cells - Hong-Feng Yuan; Chao Zhai; Xin-Long Yan; Dan-Dan Zhao; Jing-Xue Wang; Quan Zeng; Lin Chen; Xue Nan; Li-Juan He; Si-Ting Li; Wen Yue; Xue-Tao Pei (Journal of Molecular Medicine, 2012)

Isolation and identification of an acetoin high production bacterium that can reverse transform 2,3-butanediol to acetoin at the decline phase of fermentation - Xian Zhang; Tao-wei Yang; Qing Lin; Mei-juan Xu; Hai-feng Xia; Zheng-hong Xu; Hua-zhong Li; Zhi-ming Rao (World Journal of Microbiology and Biotechnology, 2011)

PTP1B inhibitor improves both insulin resistance and lipid abnormalities in vivo and in vitro - Yi-ming Ma; Rong-ya Tao; Qian Liu; Juan Li; Jin-ying Tian; Xiao-lin Zhang; Zhi-yan Xiao; Fei Ye (Molecular and Cellular Biochemistry, 2011)

Effects of explant types and media salt strength on growth and secondary metabolite accumulation in adventitious roots of Periploca sepium Bunge - Jian Zhang; Wen-Yuan Gao; Juan Wang; Xing-Lin Li (Acta Physiologiae Plantarum, 2011)

Involvement of OsNPR1/NH1 in rice basal resistance to blast fungus Magnaporthe oryzae - Jia-Xun Feng; Lin Cao; Juan Li; Cheng-Jie Duan; Xue-Mei Luo; Ning Le; Haihong Wei; Shujia Liang; Chengcai Chu; Qinghua Pan; Ji-Liang Tang (European Journal of Plant Pathology, 2011)

High efficiency of BRCA1 knockout using rAAV-mediated gene targeting: developing a pig model for breast cancer - Yonglun Luo; Juan Li; Ying Liu; Lin Lin; Yutao Du; Shengting Li; Huanming Yang; Gábor Vajta; Henrik Callesen; Lars Bolund; Charlotte Brandt Sørensen (Transgenic Research, 2011)

QSAR Study on Insect Neuropeptide Potencies Based on a Novel Set of Parameters of Amino Acids by Using OSC-PLS Method - Yong Lin; Haixia Long; Juan Wang; Mao Shu; Yuanqiang Wang; Li Wang; Zhihua Lin (International Journal of Peptide Research and Therapeutics, 2011)

A New “Switch-On” Fluorescence Chemosensor for Anions via Modulation of Intraligand and Metal-to-Ligand Charge-Transfer Emission in a Pd(II)-based Receptor - Li-Rong Lin; Qin-Juan Xu; Xin Wu; Rong-Bin Huang; LanSun Zheng (Journal of Fluorescence, 2011)

Pig transgenesis by Sleeping Beauty DNA transposition - Jannik E. Jakobsen; Juan Li; Peter M. Kragh; Brian Moldt; Lin Lin; Ying Liu; Mette Schmidt; Kjeld Dahl Winther; Brian Dall Schyth; Ida E. Holm; Gábor Vajta; Lars Bolund; et al. (Transgenic Research, 2011)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

Progressive changes of orexin system in a rat model of 6-hydroxydopamineinduced Parkinson’s disease - Cui Long-Biao; Li Bo-Wei; Jin Xiao-Hang; Zhao Lin; Shi Juan (Neuroscience Bulletin, 2010)

Geniposide inhibits interleukin-6 and interleukin-8 production in lipopolysaccharide-induced human umbilical vein endothelial cells by blocking p38 and ERK1/2 signaling pathways - Hong-Tao Liu; Jun-Lin He; Wen-Ming Li; Zhu Yang; Ying-Xiong Wang; Juan Yin; Yu-Guang Du; Chao Yu (Inflammation Research, 2010)

FAK is involved in invasion and metastasis of hepatocellular carcinoma - Jing-Song Chen; Xiao-Hui Huang; Qian Wang; Xi-Lin Chen; Xin-Hui Fu; Hao-Xiang Tan; Long-Juan Zhang; Wen Li; Jiong Bi (Clinical & Experimental Metastasis, 2010)

Identification and characterization of two Bamboo (Phyllostachys praecox) AP1/SQUA-like MADS-box genes during floral transition - Er-Pei Lin; Hua-Zheng Peng; Qun-Ying Jin; Min-Juan Deng; Tao Li; Xin-Chao Xiao; Xi-Qi Hua; Kui-Hong Wang; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (Planta, 2009)

Establishment and characterization of a fibroblast cell line from the Mongolian horse - Lin-feng Li; Wei-jun Guan; Yue Hua; Xiu-juan Bai; Yue-hui Ma (In Vitro Cellular & Developmental Biology - Animal, 2009)

Hemizygous minipigs produced by random gene insertion and handmade cloning express the Alzheimer’s disease-causing dominant mutation APPsw - Peter M. Kragh; Anders Lade Nielsen; Juan Li; Yutao Du; Lin Lin; Mette Schmidt; Ingrid Brück Bøgh; Ida E. Holm; Jannik E. Jakobsen; Marianne G. Johansen; Stig Purup; Lars Bolund; et al. (Transgenic Research, 2009)

Effect of CO2 enrichment on the glucosinolate contents under different nitrogen levels in bolting stem of Chinese kale (Brassica alboglabra L.) - Gui-xiao La; Ping Fang; Yi-bo Teng; Ya-juan Li; Xian-yong Lin (Journal of Zhejiang University-SCIENCE B, 2009)

The sources and seasonal variations of organic compounds in PM2.5 in Beijing and Shanghai - Yilun Jiang; Ximei Hou; Guoshun Zhuang; Juan Li; Qiongzhen Wang; Rong Zhang; Yanfen Lin (Journal of Atmospheric Chemistry, 2009)

Emission of fine organic aerosol from traditional charcoal broiling in China - Ximei Hou; Guoshun Zhuang; Yanfen Lin; Juan Li; Yilun Jiang; Joshua S. Fu (Journal of Atmospheric Chemistry, 2008)

The chemistry of heavy haze over Urumqi, Central Asia - Juan Li; Guoshun Zhuang; Kan Huang; Yanfen Lin; Qiongzhen Wang; Yuhong Guo; Jinghua Guo; Shulong Yu; Caixia Cui; Joshua S. Fu (Journal of Atmospheric Chemistry, 2008)

Cloning and functional characterization of PpDBF1 gene encoding a DRE-binding transcription factor from Physcomitrella patens - Ning Liu; Nai-Qin Zhong; Gui-Ling Wang; Li-Juan Li; Xiang-Lin Liu; Yi-Kun He; Gui-Xian Xia (Planta, 2007)

MHC-BPS: MHC-binder prediction server for identifying peptides of flexible lengths from sequence-derived physicochemical properties - Juan Cui; Lian Yi Han; Hong Huang Lin; Zhi Qun Tang; Li Jiang; Zhi Wei Cao; Yu Zong Chen (Immunogenetics, 2006)

A neutral protease from Bacillus nematocida, another potential virulence factor in the infection against nematodes - Qiuhong Niu; Xiaowei Huang; Lin Zhang; Yunxia Li; Juan Li; Jinkui Yang; Keqin Zhang (Archives of Microbiology, 2006)

Production of 2-(2-phenylethyl) Chromones in Cell Suspension Cultures of Aquilaria sinensis - Shu-Yuan Qi; Meng-Ling He; Li-Dong Lin; Chuan-Hai Zhang; Lan-Juan Hu; Hui-Zhen Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Suppression subtractive hybridization cloning of cDNAs of differentially expressed genes in dovetree (Davidia involucrata) bracts - Yun-Xiang Li; Li Chen; Lin Juan; Yufeng Li; Fang Chen (Plant Molecular Biology Reporter, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)